Chain-length distributions and solid content determine digestion-limiting mechanisms of wheat starch gels through cross-scale fractal network assembly - Jing Wang; Xiangqi Fan; Jiaying Shang; Zipeng Liu; Limin Li; Jing Hong; Mei Liu; Xueling Zheng; Chong Liu (Food Hydrocolloids, 2027)

Mitogenomes of three Sinoxylon species and phylogenetic analysis of Bostrichoidea (Coleoptera) - Hua-Min Fan; Xiao-Yun Wang; Kai Lin; Qian Lu; Qiu-Hong Tao; Jun Li; Xia-Lin Zheng (Molecular Genetics and Genomics, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Global, regional, and national burden of schizophrenia and its environmental drivers, 1990-2021: Retrospective analysis and projections to 2040 - Yixin Liu; Xiangyu Fan; Jiayue Yu; Shaonan Tong; Ying Sun; Pu Lei; Liangjia Wang; Min Jia; Xiancang Ma; Lichun Qiao; Peiqi Lu; Hong Li; et al. (Journal of Environmental Sciences, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Automated finite element mesh generation of damaged concrete structures using semantic point clouds - Linjie Huang; Gao Fan; Jun Li; Hong Hao (Engineering Structures, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Mechanochemical activation of industrial calcium carbide for sustainable synthesis of propargylic alcohols via its nucleophilic reaction with ketones - Hui Xu; Sinan Cheng; Zhengrun Chen; Zihao Su; Hongwei Fan; Yingzhou Lu; Hong Meng; Chunxi Li (Chemical Engineering Journal, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Mechanistic bifurcation and coordination modification in peroxymonosulfate activation by cobalt catalysts - Yan Zhao; Fan Wu; Xiaojiao Chen; Yingyi Wang; Li Hui; Hong Lin (Journal of Environmental Chemical Engineering, 2026)

Solvothermal upcycling of spent LiFePO4 cathode materials into high-voltage LiMn0.5Fe0.5PO4 via a dual-olivine intermediate - Ye Hong; Fan Wang; Chunjiao Hu; Penghui Tan; Tianhua Shang; Heng Kuang; Lingchao Kong; Jin Li; Qianqian Hu; Jian Ouyang; Zilong Tang; Shuaibo Zeng (Journal of Environmental Chemical Engineering, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Enhancing wheat yield through improved sowing uniformity in China: A meta-analysis - Peiyin Jia; Jing-Wei Fan; Xin-Mao Li; Chu-Yi Sun; Jairo A. Palta; Hong Zhao; Wen-Yuan Luo; Lan Yang; Jian Zhang; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

Diurnal differences in the effects of heat exposure on renal function: A randomized controlled crossover trial - Jintao Liu; Yuefang Li; Yarui Fan; Xiaojie Zou; Hung Chak Ho; Danfeng Zhang; Jing Zhang; Jian Song; Xu Wang; Xiuxiu Ding; Xiaoyu Jin; Lijuan Qiu; et al. (Environmental Research, 2026)

Borehole geophysical studies in glaciers. Part II: Borehole in situ observatories - Pavel G. Talalay; Xiaopeng Fan; Bing Li; Nan Zhang; Da Gong; Jialin Hong; Yazhou Li (Earth-Science Reviews, 2026)

Autothermal pyrolysis of traditional Chinese medicine residues for the sustainable products: Oxygen boundary, coupled kinetics, and product valorization - Qian Deng; Aijun Li; Yongda Huang; Yuxin Wang; Chao Liao; Yicheng Lei; Yuanyu Zhu; Yulu Fan; Hong Yao (Chemical Engineering Journal, 2026)

Cantharidin triggers cardiotoxicity via reactive anhydride-mediated covalent protein modification - Yaya Fan; Chengjiang He; Yeli Li; Ni Li; Chao Fang; Fuguo Shi; Hong Pan (Chemico-Biological Interactions, 2026)

Brown carbon optical emissions from residential coal combustion in china: Dominance of solvent-insoluble components - Fan Li; Qiaoqiao Wang; Nan Ma; Zechao Hu; Xiaocong Zhao; Ning Yang; Zheng Yang; Guangjin Liu; Yuanwei Zhong; Jiangchuan Tao; Juan Hong; Yaqing Zhou; et al. (Atmospheric Research, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Quality-aware generative distillation for robust and efficient livestock detection - Jin Liu; Weinan Hong; Lei Yao; Fanrong Kong; Zipei Fan; Lin Lei; Yuanqian Ma; Xinwei Li (Computers and Electronics in Agriculture, 2026)

Classical swine fever virus hijacks triglyceride metabolism via the NS5B-PLIN5 axis to facilitate viral replication - Xiao-Wen Li; Liang-Chun Liu; Fei-Fan Zhao; Yan-Hong Yong; Xiang-hong Ju (Veterinary Microbiology, 2026)

Electrostatically assembled gold nanocluster-enhanced porphyrinic metal-organic framework nanozymes for oxygen-boosted photodynamic therapy of hypoxic tumors - Ao He; Juan Zhou; Jing Zhu; Guojing Hong; Minglan Fan; Yuyan Bao; Rong Li; Manxiao Cheng; Xiang Ran (Journal of Photochemistry and Photobiology B: Biology, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Elucidation of a novel skatole degradation pathway and key genes in Rhodococcus rhodochrous S3 - Kaihua Pan; Rui Fan; Qi Xie; Yike Lyu; Bingjie Xu; Qian Zhu; Mingliang Zhang; Qian Li; Weihao Zhu; Yanni Huang; Qing Hong; Lina Sun (Journal of Hazardous Materials, 2026)

Improving solubility and foaming properties of Spirulina platensis protein isolate: Insights into the effect of succinylation modification on structural conformation and physicochemical properties - Xin Hong; Liuping Fan; Jinwei Li; Aiguo Luo; Liang Wang; Xiaolan Wang; Shengquan Huang (Food Hydrocolloids, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Short-chain amylopectin and long-chain amylose drive distinct wheat starch gel networks with similar low digestibility - Jing Wang; Xiangqi Fan; Jiaying Shang; Zipeng Liu; Limin Li; Jing Hong; Mei Liu; Erqi Guan; Xueling Zheng; Chong Liu (Carbohydrate Polymers, 2026)

Selenium-Related Genes Modulate Susceptibility to Parkinson’s Disease Via Combination and SNCA-Interactive Effects Rather than Independent Effects: A Case-Control Study - Hui-Hui Fan; Zhi-Hai Zeng; Shan Li; Fan Zhang; Ren-Wei Jin; Jian-Yong Wang; Bei-Lei Hu; Xiong Zhang; Jian-Hong Zhu (Biological Trace Element Research, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Rapid determination of diesel density using near-infrared and mid-infrared spectroscopy data fusion modelling - Chaomin Ding; Ying Kan; Anni Liu; Xiaoyan Guo; Zhengdong Zhang; Junting Tong; Ke Li; Fan Liu; Xiaoping Song; Yong Yan; Qi Li; Tao Hong (Fuel, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

A daily-weekly-resolved δ18O record derived from a modern giant clam shell in the northern South China Sea: Implications for paleoclimate and paleoweather reconstruction - Chengcheng Liu; Nanyu Zhao; Guozhen Wang; Fan Luo; Shan Liu; Qiuju Yang; Murong Qi; Tao Han; Gang Xue; Miaohong He; Qiuli Li; Guoqiang Tang; et al. (Chemical Geology, 2026)

Atmospheric gaseous HCl influenced by sea-land breeze circulation in a southeast Chinese coastal city - Xiaolong Fan; Lei Yao; Yee Jun Tham; Chen Yang; Yuping Chen; Huiwen Chen; Gaojie Chen; Ziyi Lin; Youwei Hong; Mengren Li; Lingling Xu; Jinsheng Chen (ENGINEERING Environment, 2026)

Long-term intercropping increases soil microbial community stability via network simplification and stochastic assembly - Pingxing Wan; Wen Yin; Pan Li; Yakov Kuzyakov; Saeed Karbin; Lianhao Zhao; Cai Zhao; Aizhong Yu; Zhilong Fan; Falong Hu; Hong Fan; Qiang Chai (Agriculture, Ecosystems & Environment, 2026)

Emerging contaminant fluorinated liquid crystal monomer 1-ethoxy-2,3-difluoro-4-(trans-4-propylcyclohexyl) benzene (EDPrB)-induced hepatotoxicity: Insights from combined transcriptomics and metabolomics approaches - Wanlun Li; Shutao Wang; Ziwei Wang; Huize Fan; Hong You (Toxicology and Applied Pharmacology, 2026)

Satellite radar reveals nearly 20% permafrost undergoing interannual subsidence in the Tibetan Plateau - Huadong Guo; Lichuan Zou; Chao Wang; Xin Li; Yixian Tang; Zhengjia Zhang; Peifeng Ma; Fan Wu; Hong Zhang (Science Bulletin, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Antifungal activity and action mechanisms of 2, 4-Di-tert-butylphenol from Bacillus amyloliquefaciens Z-7 volatile organic compounds against Verticillium dahliae - Hong Tan; Jie Zeng; Jinyi Wu; Chunsheng Wang; Lihua Zhang; Anlong Hu; Zhibo Zhao; Youhua Long; Rong Fan; Xiaoping Hu; Rongyu Li (Pesticide Biochemistry and Physiology, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Synergistic effect of IL-4 and simulated microgravity on osteogenic differentiation of periosteal stem cells - Li-Jin Liu; Fei-Xiang Lu; Xiao Yang; Yu-Bo Fan; Zhi-Hong Wu; Xin-Tong Wu; Lian-Wen Sun (Life Sciences in Space Research, 2026)

Sustainable catalyst design: Magnesia slag-doped MS-LDHs fabricated via pulsed laser trapping for efficient and green Cr(VI) adsorption - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Hong-xuan Xing; Ji-dong Li; Qiu-yu Huang; Zhe Jin; Ting-an Zhang (Journal of Cleaner Production, 2026)

Urea as a rising driver of harmful algal blooms: Integrating global patterns, metabolic pathways, and ecological consequences - Huaizhi Qin; Muhamad Syaifudin; Tangcheng Li; Wenkang Fan; Hong Du; Senjie Lin (Harmful Algae, 2026)

Controlled irradiation-engineered low-molecular-weight pectin exhibits high digestive stability and retains prebiotic activity in vivo - Zhipeng Su; Lingtao Kang; Hongbing Wang; Zixuan Li; Hui Wen; Xia Chang; Yujiao Qian; Fan Huang; Xiaopeng Li; Hong-Hui Wang; Gaoyang Li (Food Research International, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Color-tunable, time-dependent afterglow polymers from radical copolymerization: Toward multilevel encryption and dynamic anti-counterfeiting - Sicheng Cao; Qin Wu; Shihao Zhang; Yulu Hong; Li-Juan Fan (Chemical Engineering Journal, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Downregulation of UQCRC1 Expression Leads to Cognitive Decline by Disrupting the Cilia in the Dentate Gyrus - Jing Zhang; Tianyao Liu; Zonghong Long; Zuoxi Wu; Jing Luo; Fuhai Bai; Lianyu Zhou; Hong Gong; Meifeng Gong; Hong Li; Xiaotang Fan (Neuroscience Bulletin, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Machine learning revealed geochemical drivers of cadmium availability and methane emissions in hydrologically fluctuating paddy soils - Qiuyue Chen; Mengmeng Yin; Chengjie Hong; Bowen Fan; Jialin Chi; Zongqiang Zhu; Kai Liu; Xiaoxia Zhou; Liping Fang; Fangbai Li (Journal of Hazardous Materials, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Environmental challenges in advanced treatment of high-salinity mine water: A life cycle assessment perspective - Mengqing Li; Xianfeng Tan; Jianguo Fan; Hongnian Chen; Tianzuo Zhang; Changting Li; Shuo Wang; Jinglan Hong (Environmental Impact Assessment Review, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Association Between Heavy Metal Exposure and Alzheimer’s Disease Prevalence and Mortality: A Systematic Review and Meta-analysis - Yaohui Fang; Huma Shahzad; Zhi Li; Jiarong Zhang; Xinru Wang; Ziyan Qiao; Hong Qian; Qiaoqiao Xu; Yun Fan; Chuncheng Lu (Exposure and Health, 2026)

Effect of boiling time on noodle surface tackiness: Roles of gluten network and broth components in steamed-then-boiled noodles - Yijun Fan; Mingyi Shen; Ruifang Wang; Zhengbiao Gu; Yan Hong; Zhaofeng Li; Caiming Li; Xiaofeng Ban; Li Cheng (Journal of Cereal Science, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

Selective hydrogenation of nitriles to primary and secondary amines via Ni0/Ni2+ dual sites - Tongtong Fan; Jiaheng Qin; He Wen; Siyu Li; Hong Zhao; Tong Li; Xiao Zhang; Jiantai Ma; Yu Long (Fuel, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Efficient capillary electrophoretic analysis of anthraquinones and phenolic acids in functional foods using a novel deep eutectic solvent–in–deep eutectic solvent microemulsion - Kai-Yang Fan; Shi-Qi Niu; Tian Zhang; Jun Cao; Li-Hong Ye (Food Chemistry, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Predicting pedestrian-level melanopic illuminance from multi-source urban data with explainable machine learning - Wenjin Hong; Zhe Kong; Peng Tang; Ziqi Fan; Rui Duan; Zixuan He; Xintong Li; Xinyi Wu (Building and Environment, 2026)

Ten questions concerning Large Language Models (LLMs) for building applications - Nan Ma; Rania Labib; Robert Amor; Adrian Chong; Cheng Fan; Kasimir Forth; Xiaoqin Fu; Stefan Fuchs; Tianzhen Hong; Nina Klimenkova; Jabeom Koo; Shundong Li; et al. (Building and Environment, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

Future Directions of Seaweed-based Bioeffectors and Biofertilizer - Muhamad Syaifudin; Jialong Xu; Wenkang Fan; Mohamed G. Moussa; Chenhui Zhong; Tangcheng Li; Hong Du (Journal of Soil Science and Plant Nutrition, 2026)

Growth environment of the Pacific oyster (Crassostrea gigas) reefs recorded by shells and sediment since mid-Holocene on the coastal plain of the Western Bohai Sea, China - Yi-ming Huo; Yue Zhao; Chang-fu Fan; Yan-he Li; Bin Hu; Zhi-wen Shang; Fu Wang; Hong Wang (Geo-Marine Letters, 2026)

Hydrological processes govern methane flux fluctuations in a subtropical floodplain - Xueran Wang; Rongrong Wan; Guishan Yang; Xiaosong Zhao; Bing Li; Xingwang Fan; Yixue Hong; Haoran Wang; Jipeng Song; Zhiyu Song; Yu Jiang (Agricultural and Forest Meteorology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Organic chemicals of Arctic concern in Russian coastal seas - Xi-Ze Min; Xianming Zhang; Zhi-Yong Xie; Anatoly Nikolaev; Katrin Vorkamp; Jian-Min Ma; Lars-Otto Reiersen; Li Li; Ming-Hong Cai; Nan-Qi Ren; Yi-Fan Li; Zi-Feng Zhang; et al. (Science Bulletin, 2026)

Hydrological seasonality shapes diel methane emission variations in China’s largest floodplain lake - Xueran Wang; Rongrong Wan; Xiaosong Zhao; Bing Li; Xingwang Fan; Qitao Xiao; Haoran Wang; Jipeng Song; Zhiyu Song; Yu Jiang; Yixue Hong; Guishan Yang (Journal of Hydrology, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

The primary sources of ROx radicals in atmosphere: Oxidative capacity and self-purifying effect - Gaojie Chen; Ziyi Lin; Xiaoting Ji; Lingling Xu; Xiaolong Fan; Mengren Li; Youwei Hong; Jinsheng Chen (Journal of Environmental Sciences, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Longitudinal biomarker trajectories and their prognostic utility for 21-day mortality in burn patients with sepsis: a retrospective cohort study - Jiaqi Lou; Hong Kong; Jiliang Li; Ziyi Xiang; Xiaoyu Zhu; Shengyong Cui; Neng Huang; Sida Xu; Guoying Jin; Xin Le; Youfen Fan (Inflammation Research, 2026)

Experimental Analysis of Traction Performance of Tracked Mining Vehicles in Deep-Sea Sediments - Lixin Xu; Yajiao Liu; Xiu Li; Zhichao Hong; Menghao Fan; Yanli Chen; Haonan Wei (Journal of Marine Science and Engineering, 2026)
The complex seabed topography and mechanical properties of deep-sea sediments impose stringent requirements on the traction performance and locomotion stability of tracked mining vehicles. Experimental investigations on the coupled effects of grouser geometry and operating conditions on traction remain limited. To address this, rheological tests and multi-parameter traction experiments were conducted. Deep-sea sediments were modeled as a power-law fluid to capture their non-Newtonian behavior, considering particle size distribution, water content, and compaction state. Using a self-designed traction test apparatus, the influences of grouser geometry and operating parameters on traction force were systematically analyzed. Results indicate that both grouser configuration and operating conditions significantly affect traction force magnitude and stability. Rectangular grousers, exhibiting more uniform stress distribution and pronounced shear bands, demonstrated enhanced traction efficiency and locomotion stability under high-load, low-speed conditions. When the grouser length was 30 mm and the traveling speed was maintained at 7–12 mm/s, sediment fluidization was significantly mitigated, improving traction performance. Furthermore, a spacing of at least 20 mm between adjacent grousers produced a synergistic effect, increasing sediment shear strength by approximately 30–40%. These findings provide quantitative guidance for grouser design and operational optimization of tracked deep-sea mining vehicles.

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Leonurine alleviates retinal ischemia-reperfusion injury by inhibiting microglia activation - Jingchang Yuan; Miao Wei; Xiaochen Wang; Sisi Tan; Yujia Huo; Ruotong Ouyang; Xiao Fan; Hong Li (Toxicology and Applied Pharmacology, 2026)

Editor's note to “A sublethal dose of neonicotinoid imidacloprid precisely sensed and detoxified by a C-minus odorant-binding protein 17 highly expressed in the legs of Apis cerana” [Sci. Total Environ. 885 (2023) 163762] - Yi-Lei Qiu; Fan Wu; Li Zhang; Hu-Qiang Jiang; Jin-Tao Chen; Hong-Liang Li (Science of The Total Environment, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

CDANet: A context-detail aware network for marine oil spill detection in SAR imagery - Zhe Wang; Hong Zhang; Zihuan Guo; Yukun Fan; Lu Xu; Xiaoming Li; Chao Wang (Journal of Hazardous Materials, 2026)

Turning gel ratios to engineer 3D-printed hybrid gel-based foamed emulsion - Xin Hong; Zhenhua Duan; Liuping Fan; Jinwei Li (Journal of Food Engineering, 2026)

Effects of different drying methods on the physicochemical properties, antioxidant activity and gut microbiota fermentation behaviours of polysaccharides from Schizophyllum commune - Lihong Fan; Chaomin Yin; Haina Ma; Jing Wen; Maofen Yi; Zhenshun Li; Xiuzhi Fan; Defang Shi; Zhicheng Huang; Jianhui Qiu; Hong Gao (Food Research International, 2026)

Comparison of physicochemical properties of water- and alkaline-extracted polysaccharides from Schizophyllum commune and their anti-obesogenic effects in vivo - Chen Li; Chaomin Yin; Jiangtao Li; Jing Wen; Lihong Fan; Haina Ma; Xiuzhi Fan; Defang Shi; Wei Yu; Jianhui Qiu; Hong Gao (Food Chemistry, 2026)

Interplay and integrated regulation of astaxanthin-lipid biosynthesis in microbial systems: A review from metabolic pathway cross-talk to biotechnological optimization - Zhipeng Li; Lifen He; Yuanzhen Song; Danling Tang; Fan Feng; Shaofan Cha; Tao Hong; Mingjing Zheng; Xiping Du; Yanbing Zhu; Yuanfan Yang; Zedong Jiang; et al. (Food Microbiology, 2026)

β-defensin 2 enhances antiviral immunity via autophagy regulation during Micropterus salmoides rhabdovirus (MSRV) infection and promotes survival in largemouth bass - Yong-Fei Zhu; Xue-Ni Wang; Yi-Fan Hu; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2026)

Smartphone-based vehicle-road contact-point response identification with unknown vehicle parameters - Zhen Peng; Jun Li; Hong Hao; Gao Fan; Lalinda Karunaratne (Engineering Structures, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Surface reaction regulation for high-voltage and safe quasi-solid-state lithium metal batteries - Zehui Fan; Yuansheng Liu; Hai Su; Sijia Chi; Qiujiang Dong; Yingxin Liu; Li Wang; Quan-Hong Yang; Yunhua Xu (Chemical Engineering Journal, 2026)

Schizophyllum commune polysaccharide ameliorates diet-induced obesity by regulating the Faecalibaculum rodentium/indole-3-lactic acid/microRNA axis - Chaomin Yin; Chen Li; Xiuzhi Fan; Defang Shi; Jiangtao Li; Jianhui Qiu; Fen Yao; Wei Yu; Hong Gao (Carbohydrate Polymers, 2026)

Development and application of a new simple algorithm for stochastic modeling of daily ground snow loads: A case study in Northeastern China - Huamei Mo; Yuanyuan Li; H.P. Hong; Guolong Zhang; Qingwen Zhang; Feng Fan (Cold Regions Science and Technology, 2026)

Genetic and transcriptomic analysis of microbial electro-extraction for releasing metals from spent Lithium-Ion batteries - Min Li; Danni Zhang; Dawn E. Holmes; Qiuli Xia; Hong Wang; Yongqiang Fan; Hao Song; Dake Xu; Derek R. Lovley (Bioresource Technology, 2026)

Deciphering the role and mechanism of biochar dosage and inoculum-to-substrate ratio in modulating interspecies electron transfer and alleviating acid inhibition - Yu-Hong Qiu; Zi-Fan Wu; Jia-Bing Li; Zhi-Man Yang (Biomass and Bioenergy, 2026)

m6A Modification Genetic Variants Associated with Autism Spectrum Disorder Risks - Haoxue Wang; Shuai Zhao; Yanlin Chen; Fang Hou; Kaiheng Zhu; Rundong Liu; Zhen Xiang; Qianhui Chen; Hong Fan; Mengyuan Huang; Zhike Wang; Jiao Zhang; et al. (Molecular Neurobiology, 2026)

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

HINT2-Mediated Mitochondrial Modulation Contributes to G-CSF Neuroprotection in Alcohol Use Disorder-Related Ischemic Stroke - Zhi-Chen Guo; Hong-Wei Zhang; Hai-Jian Zhao; Zhi-Li Zhao; Dan Shen; Xiao-Fang Li; Hui-Fang Xi; Teng Fan; Jie Yin; Ning An; Xiu-Qin Yue; Wei-Wei Wang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Ecological functions coupled with plasmid and phage-mediated dissemination drive the global prevalence of high-risk antimicrobial resistance genes in influent - Fang Huang; Shu-Hong Gao; Yanmei Zhao; Qi Liu; Rui Gao; Zihan Dai; Jingni Xie; Bin Liang; Jinsong Liang; Lu Fan; Xin Li; Ai-Jie Wang (Water Research, 2025)

Corrigendum to “Biochar-amended coastal wetland soil enhances growth of Suaeda salsa and alters rhizosphere soil nutrients and microbial communities” [Sci. Total Environ. 788 (2021), 147707] - Jing-Fang Cai; Fan Jiang; Xuan-Shao Liu; Kai Sun; Wei Wang; Ming-Xiang Zhang; Hong-Li Li; Wei-Jing Kong; Fei-Hai Yu (Science of The Total Environment, 2025)

Precise molecular spacer engineering for tumor-responsive pKa tuning: a pan-cancer imaging platform for evaluating tumor microenvironment reprogramming capability - Hong Zhang; Fei-Fan Xiang; Ding-Heng Zhou; Yan-Hong Liu; Zhou-Yu Wang; Shan-Yong Chen; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Synoptic-scale precipitation events recorded by high-resolution intra-shell δ18O of land snail in the Asian monsoon marginal zone - Qian Zhang; Jibao Dong; Guozhen Wang; Fan Luo; Ya-na Jia; Chengcheng Liu; Xiulan Zong; Xiangzhong Li; John Dodson; Hong Yan (Quaternary Science Reviews, 2025)

Functional characterization of GmSRS14 in regulating root nodule development of soybean - Kangjun Fan; Yue Wu; Yonghua Qin; Hongzao He; Lu Lv; Gang Li; Jiao Liu; Rui Qin; Hong Liu (Journal of Plant Physiology, 2025)

Seasonal and inter-annual dynamics of water vapor flux based on five-year eddy covariance measurements over an alpine grassland in arid Central Asia - Baoxiang Fan; Haijun Peng; Hu Yao; Kaihui Li; Bing Hong (Journal of Hydrology, 2025)

The embodied agricultural NH3 emissions in China's inter-provincial trade and the implied environmental inequities - Lu Lu; Zebin Zhao; Jinpan Jiang; Fan Meng; Ziyi Wang; Changshun Wang; Jingchao Li; Hong Qi; Donglei Fu (Journal of Cleaner Production, 2025)

Decoding the aroma signature of Jinhua ham: Flavoromics-driven machine learning models for age-discrimination with hardware implementation - Wenlu Li; Xinwei Fan; Hong Zeng; Yanbo Wang (Food Research International, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Effects of dietary docosahexaenoic acid on the growth, immune responses and resistance of sea cucumber Apostichopus japonicus against Vibrio splendidus infection - Hong Fan; Yina Shao; Xuelei Wang; Kaiyu Chen; Si Zhu; Chenghua Li (Fish & Shellfish Immunology, 2025)

Automated surface damage detection and quantification in concrete structures using semantic point clouds - Linjie Huang; Gao Fan; Jun Li; Shihong Chen; Zhen Peng; Hong Hao (Engineering Structures, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

Integration of transcriptomic and chemical analysis reveals key regulatory mechanisms involved in color variation between red and white flowers of Camellia semiserrata - Hong Jiang; Menglong Fan; Ying Zhang; XinLei Li (Genetic Resources and Crop Evolution, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Size-Dependent Salinity Tolerance and Osmotic Regulation in Juvenile Lateolabrax japonicus - Pengcheng Gao; Zhichang Yuan; Yanwu Ma; Yiming Li; Zongli Yao; Kai Zhou; Zhen Sun; Yuxing Wei; Hong Liu; Fan Yang; Yan Li; Qifang Lai (Fishes, 2025)
Salinity is one of the most critical environmental factors for fish, influencing their reproduction, growth, and physiological and metabolic activities. Lateolabrax japonicus is a major commercially important marine fish that has been widely cultured in China. However, there are few reports on the growth tolerance of fish juveniles of different species under various salinity conditions. In this study, we investigated the effects of acute low-salt stress on the survival, plasma osmolality, blood ion concentration, and Na+/K+-ATPase (NKA) activity in L. japonicus juveniles of two size groups. Our findings revealed no significant difference in survival rates between 5 cm and 10 cm juveniles at salinities of 0.2, 1, 3, 5, 10, 15, and 25. Plasma osmolality and blood ions exhibited a “decrease-increase-stabilization” pattern; 5 cm juveniles stabilized at 6 h at all salinities, whereas 10 cm juveniles required 48 h to stabilize at a salinity of 1, with isosmotic points of 10.91 and 11.00, respectively. Gill and kidney NKA activity followed an “increase-decrease-stabilization” pattern, with 5 cm juveniles achieving stability 12–24 h earlier than 10 cm individuals under low salinities (1, 3, 5). In conclusion, 5 cm L. japonicus juveniles exhibited superior low-salinity tolerance, accelerated osmoregulatory responses, and enhanced adaptation compared to 10 cm juveniles. These findings strongly support the prioritizing of smaller-sized L. japonicus for low-salinity aquaculture practices.

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

Is destabilized coupled flat plate membrane technology valuable for high-salinity mine water treatment? - Liyao Wang; Xianfeng Tan; Jianguo Fan; Hongnian Chen; Tianshu Xu; Mengqing Li; Jinglan Hong (Environmental Research, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Revisiting the genesis of Bi-Te-Au-S associations: Implications for the ore-forming processes in gold deposits - Gao-Hua Fan; Jian-Wei Li; Zhan-Ke Li; Xue-Feng Yu; Xiao-Dong Deng; Jin-Hao Liu; Hang-Jin Jiang; Hong-Jun Sun; Tian-Ming Zhang (Chemical Geology, 2025)

Engineering resistance genes against tomato brown rugose fruit virus - Junzhu Wang; Tianxin Shen; Mengjie Song; Jiayi Fan; Yiqing Li; Toto Zen Chin; Yidan Yu; Fan Huang; Xiuling Yang; Changbao Li; Xueping Zhou; Chuanyou Li; et al. (Science China Life Sciences, 2025)

Synergistic effects of slow-release fertilizer and biochar on crop yield and soil carbon-nitrogen dynamics under reduced nitrogen input - Lianhao Zhao; Wen Yin; Qiang Chai; Pan Li; Zhipeng Guo; Zhilong Fan; Falong Hu; Cai Zhao; Aizhong Yu; Pingxing Wan; Wei He; Hong Fan; et al. (Agriculture, Ecosystems & Environment, 2025)

Melatonin improves growth and slaughter performance of broilers by regulating satellite cell proliferation via RORα nuclear receptor - Shuhui Ma; Lina Dong; Aili Fan; Yang Li; Yuzhe Fan; Jiayin Liu; Liang Hong; Zonghui Zuo; Daowen Li; Gang Xu (Research in Veterinary Science, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Long-term stable and temperature-responsive oleofoams based on candelilla wax: Whipping process and formation mechanism - Xin Hong; Liuping Fan; Jinwei Li (Food Structure, 2025)

Pollutant distribution in vertebrates across scales: Organs, cells, and organelles - Bo Ren; Yufei Zhao; Xiangrui Wang; Mengjing Wang; Ying Wang; Xiaomin Li; Wen-Hong Fan (Environmental Pollution, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Extensive Introgression Failed to Erode Species Boundaries Among Multiple Sympatric Closely Related Species of Roscoea - Hong‐Fan Chen; Ryan Andrew Folk; Ya‐Li Wang; Wen‐Jing Wang; Guo‐Jun Shao; Mei‐Yuan Huang; Xiang‐Qin Yu; Li Li; Jian‐Li Zhao (Molecular Ecology, 2025)
How species boundaries are maintained among sympatric closely related species experiencing gene flow is a puzzling question in evolutionary biology. Although introgression is commonly documented, the dynamics and gene function of introgression have rarely been explored to probe why frequent introgression does not necessarily destroy species boundaries in sympatry. In this study, we employ whole‐genome resequencing data to examine introgression among five closely related species of Roscoea that coexist in a ‘sky island’ with seventeen distinct morphological traits. Our findings reveal that introgression has led to the phylogenomic discordance between nuclear and chloroplast genomes among these morphologically distinct species. Additionally, introgression is predominantly asymmetrical in both intensity and gene function, particularly concerning recombination. Notably, the majority of gene functions associated with introgressed loci are unrelated to reproductive processes. Our results suggest that closely related species with incomplete allele assortment can coexist despite theoretical predictions, highlighting the semipermeable nature of species boundaries as reproductive isolation develops. This provides a critical conceptual framework for understanding the interplay between introgression and species persistence. Our finding offers insights into how related sympatric species boundaries can be maintained in the face of frequent asymmetrical gene introgression.

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

The Mechanism of the Effect of FCC Slurry Oil Blending Ratio on the Colloidal Stability and Asphaltene Aggregation Behavior of Low-Sulfur Marine Fuel Oil - Aigang Li; Shengjun Guo; Jianwen Deng; Hong Chen; Jinxuan Wu; Ru Jiang; Jing Tan; Lihua Cheng; Libo Zhang; Qinzhen Fan (Journal of Marine Science and Engineering, 2025)
Addressing IMO 2020 compliance, this study investigates marine fuel oil production from hydrotreated residues, focusing on mitigating excessive total sediment potential (TSP) caused by over-hydrotreatment. This study systematically investigates the impact of blending ratios of Fluid Catalytic Cracking (FCC) slurry oil with Residue Desulfurization (RDS) heavy oil on TSP, colloidal stability, and asphaltene structure evolution. Techniques such as XRD, SEM, and XPS were employed to analyze the structural changes in asphaltenes during the TSP exceeding process. The results indicate that as the FCC slurry oil blending ratio increases, TSP in the blended oil initially rises and then decreases. The peak TSP value of 0.41% occurs at a 10% FCC slurry oil blending ratio, primarily due to high-saturation hydrocarbons in RDS heavy oil disrupting the colloidal stability of asphaltenes in FCC slurry oil. When the blending ratio reaches 25%, TSP significantly decreases to 0.09%, attributed to the solubilizing effect of high aromatic compounds in the FCC slurry oil on the asphaltenes. The ω(Asp)/ω(Res) ratio mirrors the TSP trend, and the colloidal solubilizing capacity of asphaltenes increases with the blending ratio. Asphaltenes in RDS heavy oil exhibit a spherical structure, whereas those in FCC slurry oil show a layered structure. The precipitated asphaltenes in the blends primarily result from the aggregation of asphaltenes in FCC slurry oil, with heteroatoms (N, S, O) mainly originating from RDS heavy oil asphaltenes. During the early stage of blending, TSP formation is dominated by FCC slurry oil asphaltenes, but increasing the aromatic content in the system can significantly reduce TSP. This work provides theoretical and technical support for optimizing marine fuel blending processes in petrochemical enterprises.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Discovery of undescribed schinortriterpenoids from Schisandra chinensis by molecular networking and their neuroprotective effects - Peng Jiang; Yu-Meng Luo; Xin-Yuan Li; Shu-Jun Zhang; Wei Guan; Anam-Naseem; Yu-Hang Fan; Qing-Shan Chen; Li-Li Zhang; Hong-Yan Yao; Xiao-Xue He; Hai-Xue Kuang; et al. (Phytochemistry, 2025)

Specific catalytic hydrogenation of 2-butyne-1,4-diol to butane-1,4-diol - Li Li; Xian-Yong Wei; Shun-Hong Lv; Xiang Bai; Yierxiati Dilixiati; Jun-Long Wang; Xiao-Yan He; Zhi-Min Zong; Xing Fan (Fuel, 2025)

Crop rotation and organic fertilizer maintains diversity and activity of cbbL-carrying CO2-fixing bacteria in reclaimed coal mining soils - Shuning Bai; Meihua Fan; Min Wu; Xiaolong Sui; Yibo Song; Yunlong Jiang; Huisheng Meng; Yulin Liu; Xiangying Wang; Xianjun Hao; Yi Li; Jianping Hong; et al. (European Journal of Soil Biology, 2025)

A novel fully coupled thermo-hydro-mechanical-damage model for hydraulic fracture propagation in fractured geothermal reservoirs - Yaoyao Zhang; Yanyan Li; Hong Zheng; Binghong Fan (Computers and Geotechnics, 2025)

Engineered flower-shaped MXene-copper nanowire composite facilitate mechanically tuned and sensitive field-effect transistors in miniaturized portable devices toward noninvasive NSCLC prognostic monitoring - Chengling Zhao; Bing Xia; Zhao Jin; Zhenkai Fan; Qiao Ge; Haining Hong; Haiwei Sang; Lixiang Li; Ansheng Wang (Chemical Engineering Journal, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

A Multi-Scale Contextual Fusion Residual Network for Underwater Image Enhancement - Chenye Lu; Li Hong; Yan Fan; Xin Shu (Journal of Marine Science and Engineering, 2025)
Underwater image enhancement (UIE) is a key technology in the fields of underwater robot navigation, marine resources development, and ecological environment monitoring. Due to the absorption and scattering of different wavelengths of light in water, the quality of the original underwater images usually deteriorates. In recent years, UIE methods based on deep neural networks have made significant progress, but there still exist some problems, such as insufficient local detail recovery and difficulty in effectively capturing multi-scale contextual information. To solve the above problems, a Multi-Scale Contextual Fusion Residual Network (MCFR-Net) for underwater image enhancement is proposed in this paper. Firstly, we propose an Adaptive Feature Aggregation Enhancement (AFAE) module, which adaptively strengthens the key regions in the input images and improves the feature expression ability by fusing multi-scale convolutional features and a self-attention mechanism. Secondly, we design a Residual Dual Attention Module (RDAM), which captures and strengthens features in key regions through twice self-attention calculation and residual connection, while effectively retaining the original information. Thirdly, a Multi-Scale Feature Fusion Decoding (MFFD) module is designed to obtain rich contexts at multiple scales, improving the model’s understanding of details and global features. We conducted extensive experiments on four datasets, and the results show that MCFR-Net effectively improves the visual quality of underwater images and outperforms many existing methods in both full-reference and no-reference metrics. Compared with the existing methods, the proposed MCFR-Net can not only capture the local details and global contexts more comprehensively, but also show obvious advantages in visual quality and generalization performance. It provides a new technical route and benchmark for subsequent research in the field of underwater vision processing, which has important academic and application values.

New anti-inflammatory limonoids from the fruits of Melia azedarach - Fan Cao; Jin-Huang Shen; Zhi-Jun Li; Wen-Lu Wang; Zhen-Wei Chen; Yong-Hong Zhang; Xin-Hua Ma (Natural Product Research, 2025)

Embryonic exposure to GenX causes reproductive toxicity by disrupting the formation of the blood-testis barrier in mouse offspring - Zhencheng Fan; Runyang Hong; Shuhao Li; Liang Kong; Qiyue Zhou; Tan Ma; Hao Chen; Chun Pan (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Impact of different green manure crops or fallow on yield and quality of a Chinese cabbage - Cai Zhao; Li Jin; Hong Fan; Yu Jia; Zhilong Fan; Wen Yin; Aizhong Yu; Falong Hu; Wei He; Qiang Chai (Plant and Soil, 2025)

Strong interannual variation of green tides in the southern Yellow Sea: Crucial factors and implications on management strategies - Yi-Fan Li; Hui-Xia Geng; Xin Hong; Fan-Zhou Kong; Ren-Cheng Yu (Marine Pollution Bulletin, 2025)

A global meta-analysis reveals effects of heavy metals on soil microorganisms - Dale Li; Xiujuan Zhang; Hong Zhang; Qirui Fan; Baobei Guo; Junjian Li (Journal of Hazardous Materials, 2025)

Valuation of the 2020 gross ecosystem product of China and analysis of driving factors - Kairui Li; Hong Fan; Jiani Ouyang; Peiwen Yao (Journal of Cleaner Production, 2025)

Sustainable fabrication of fluorescent spiropyran-functionalized chitin nanofibers via amino-yne click chemistry for UV-blocking and smart environmental monitoring - Juan Yu; Bowen Li; Yingyin Liu; Hanlu Ji; Liang Liu; Hong Sun; Yimin Fan (Chemical Engineering Journal, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Dimensionality control of chiral covalent organic frameworks for enhanced asymmetric catalysis - Kai Zhang; Yuexin Zheng; Hong Chen; Dexuan Cai; Xihao Tang; Shengrun Zheng; Mubiao Xie; Jun Fan; Yuwei Zhang; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2025)

Remarkable metabolic reconfiguration due to three classical nitrogen sources in Gracilariopsis lemaneiformis (Rhodophyta) - Wenkang Fan; Chunyou Yang; Dingzhi Song; Peilin Ye; Honghao Liang; Chunping Huang; Muhamad Syaifudin; Chenhui Zhong; Tangcheng Li; Hong Du (Algal Research, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Anti-inflammatory and hepatoprotective effects of galactose-rich heteropolysaccharides from Laoshan green tea and its physicochemical properties - Shuying Lan; Rongshen Wang; Hong Gao; Mengyao Zhao; Huiting Li; Fan Liu; Rui Geng; Yuxin Wang; Xiaoxiao Liu; Chenggang Song; Wanzhong Li (Natural Product Research, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

RIG-I-driven CDKN1A stabilization reinforces cellular senescence - Cui Wang; Xiaoyu Jiang; Hong-Yu Li; Jianli Hu; Qianzhao Ji; Qiaoran Wang; Xiaoqian Liu; Daoyuan Huang; Kaowen Yan; Liyun Zhao; Yanling Fan; Si Wang; et al. (Science China Life Sciences, 2025)

The Application of MicroRNAs in Traumatic Brain Injury: Mechanism Elucidation and Clinical Translation - Hong Wang; Xiaolin Fan; Yuhao Zhang; Ning Ma; Liang Li; Qing Lu; Qi Wang; Boya Yu; Xiao Li; Junhong Gao (Molecular Neurobiology, 2025)

Isolation and identification of a novel bisacodyl analogue, bisacodyl dicycloproyl carboxylate, as a potential illegal additive in a dried plum product advertised for weight loss - Xian-Xian Li; Feng Jiang; Hong Yu; Xiao-Jing Huang; Jing-Xian Zhang; Jin-Tao Xia; Ying-ying Ran; Fan Huang; Jian Sun; Qing Hu (Food Additives & Contaminants: Part A, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Quantitative analysis of influencing factors to aerosol pH and its responses to PM2.5 and O3 pollution in a coastal city - Ke Xu; Liqian Yin; Qiaoling Chen; Dan Liao; Xiaoting Ji; Keran Zhang; Yu Wu; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Zhi Huang; et al. (Journal of Environmental Sciences, 2025)

Crystal facet effect of the support in Ni/La2O2CO3 catalysts for toluene steam reforming - Shou-Yong Jiang; Yang Du; Yun-Jie Li; Zhi-Bin Wang; Hong-Xia Fan; Shou-Dong Xu; Zhen-Yi Du; M.D. Isobaev; Wen-Ying Li (Fuel, 2025)

No tillage with straw mulching enhanced radiation use efficiency of wheat via optimizing canopy radiation interception and photosynthetic properties - Pan Li; Wen Yin; Lianhao Zhao; Pingxing Wan; Zhilong Fan; Falong Hu; Yunyou Nan; Yali Sun; Hong Fan; Wei He; Qiang Chai (Field Crops Research, 2025)

Effect of compound exposure to snowstorm and cold spell on acute myocardial infarction mortality - Jihong Hu; Zhiwei Li; Jingli Zhu; Qin He; Wenjun Cheng; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Xiuya Xing; Jian Cheng (Environmental Research, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Flexible self-decoupled pressure/proximity/temperature sensor for composite stimulus sensing with low signal crosstalk - Qi Hong; Junjie Qiu; Jianhong Hao; Zihan Lin; Ziyuan Zhou; Xishun Ruan; Tianxu Zhang; Fan Yao; Zhitong Wang; Zhaobin Li; Weiqiang Hong; Xianghui Li; et al. (Chemical Engineering Journal, 2025)

Probing the microwave induced overheating at electrode surface using a combined electrochemical and fluorescence method - Zongliang Kou; Zhenyu Zhao; Hong Li; Ang Li; Kai Liu; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2025)

Triethoxysilane-enhanced graphene/carbon nanoparticles conductive network for multifunctional fabric electronics with pressure, temperature and strain sensing capabilities - Yunong Zhao; Jianhong Hao; Zihan Lin; Shaowen Mou; Shujing Feng; Fan Yao; Ziyuan Zhou; Zhitong Wang; Zhaobin Li; Xianghui Li; Xiaowen Zhu; Tianxu Zhang; et al. (Chemical Engineering Journal, 2025)

The chromosome-scale genomes of two cultivated safflowers (Carthamus tinctorius) provide insights into the genetic diversity resulting from domestication - Shuo Liu; Saimire Aishan; Qiuyu Liu; Lu Lv; Kang Ma; Kangjun Fan; Kehui Zhang; Yonghua Qin; Gang Li; Xueli Hu; Zunhong Hu; Junwei He; et al. (Theoretical and Applied Genetics, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Constructions and immunogenicity evaluations of two porcine epdemic diarrhea virus-like particle vaccines - Hong Xu; Mengdi Yang; Shiyu Liu; Fangyuan Zheng; YuPeng Li; Yunchuan Li; Chuanhong Wang; Jiali Qian; Yongxiang Zhao; Shanshan Yang; Min Sun; Xu Song; et al. (Veterinary Microbiology, 2025)

Porcine antibodies reveal novel non-neutralizing universal epitopes on FMDV and their overlaps with neutralization sites - Ying Sun; Shenglin Huang; Fengjuan Li; Shulun Huang; Pinghua Li; Qiongqiong Zhao; Tao Wang; Huifang Bao; Yuanfang Fu; Pu Sun; Xingwen Bai; Hong Yuan; et al. (Veterinary Microbiology, 2025)

Thioketal-photocage: a universal modification strategy for constructing new photochemical tools for real-time imaging in living cells - Ding-Heng Zhou; Shan-Yong Chen; Yan-Zhao Liu; Hong Zhang; Jun-Mei Li; Qian Zhou; Fei-Fan Xiang; Xiao-Qi Yu; Kun Li (Science Bulletin, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

TACMT: Text-aware cross-modal transformer for visual grounding on high-resolution SAR images - Tianyang Li; Chao Wang; Sirui Tian; Bo Zhang; Fan Wu; Yixian Tang; Hong Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Missing data imputation for structural health monitoring using unsupervised domain adaptation and pretraining techniques - Wenhao Zheng; Jun Li; Hong Hao; Gao Fan (Engineering Structures, 2025)

The structures of two polysaccharides from Fructus Corni and their protective effect on insulin resistance - Guang-Yuan Ma; Lu-Kuan Hou; Jia-Hui Guo; Jing-Chun Sun; Qiuna Nong; Yu-Fan Wang; Sheng-Wei Hu; Wen-Jing Zhao; Jin Tan; Xiao-Feng Liu; Yuan Guo; Bo-Jing Zhang; et al. (Carbohydrate Polymers, 2025)

Global analysis of fungal biosynthetic gene clusters reveals the diversification of diketopiperazine biosynthesis - Bin Wei; Ti-Ti Ying; Hua-Wei Lv; Zhen-Yi Zhou; Hai Cai; Gang-Ao Hu; Hui-Min Liang; Wen-Chao Yu; Yan-Lei Yu; Ai-Li Fan; Kui Hong; Xing-Nuo Li; et al. (Bioresource Technology, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

Urea Amidolyase as an Enzyme for Urea Utilisation in Phytoplankton: Functional Display in Chlamydomonas reinhardtii - Honghao Liang; Tangcheng Li; Yuanhao Chen; Jingtian Wang; Muhammad Aslam; Huaizhi Qin; Wenkang Fan; Hong Du; Shuh‐ji Kao; Senjie Lin (Molecular Ecology, 2025)
Urea is an important source of nitrogen for many phytoplankton with the potential to stimulate harmful algal blooms, but the molecular machinery underpinning urea uptake and assimilation by algae is not fully understood. Urease (URE) is commonly regarded as the responsible enzyme, but urea amidolyase (UAL), albeit known to exist, has hardly been studied. Here, the species distribution, expression patterns and functional roles of UAL are examined. We found a widespread occurrence of UAL across six major phytoplankton lineages, along with evidence of a potential URE‐independent evolutionary trajectory and lineage‐specific losses. Quantitative analyses based on marine planktonic metagenomes and metatranscriptomes revealed that UAL is as prevalent as URE, but exhibits higher expression levels in phytoplankton than in bacteria, suggesting that UAL plays a crucial role in nitrogen nutrition in marine phytoplankton. Furthermore, using the CRISPR/Cas9 genome editing method and Chlamydomonas reinhardtii as the algal model, we showed that DUR2 in UAL is essential for urea utilisation, as its knockout completely abolishes the ability of algae to grow under urea as the sole nitrogen source. This study unveils an unappreciated mechanism in algae for utilising urea as a nutrient, underscores the need to consider both URE and UAL enzyme systems to model urea utilisation by algae and provides a crucial gene ( DUR2 ) as a potential genetic marker for detecting the contribution of UAL to urea utilisation in phytoplankton.

Insights into hepatotoxicity of fluorinated liquid crystal monomer 1-ethoxy-2,3-difluoro-4-(trans-4-propylcyclohexyl) benzene (EDPrB) in adult zebrafish at environmentally relevant concentrations: Metabolic disorder and stress response - Wanlun Li; Shutao Wang; Huize Fan; Ziwei Wang; Yingying Liu; Hong You (Journal of Hazardous Materials, 2025)

Automatic complex concrete crack detection and quantification based on point clouds and deep learning - Shihong Chen; Gao Fan; Jun Li; Hong Hao (Engineering Structures, 2025)

Green fabrication of polyamide nanofiltration membranes with ultra-low chemical consumption by vacuum filtration-spraying assisted interfacial polymerization - Hong-Yu Fan; Cheng-Ye Zhu; Yu-Ren Xue; Jin-Bo Li; Chao Zhang; Tian-Yu Zhang; Li-Wu Fan; Zhi-Kang Xu (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Structure characteristics of a novel pectic polysaccharide from Fructus Corni and its protective effect on alcoholic fatty liver - Hong-Xin Bai; Yu-Xuan Gao; Shuyao Wang; Guang-Yuan Ma; Wenjing Zhao; Xiao-Qiang Li; Yu-Fan Wang; Qiu-Na Nong; Yu-Bo Wang; Jin Tan; Qimei Duan; Wei Cao (Carbohydrate Polymers, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Erwinia aeris sp. nov., A Novel Bacterium Isolated from the Surface of an Ore in Hubei Province, China - He-Bao Guo; Hong-Tu Zhu; Yi-Fan Zhang; Fu Yang; Xiao-Tong Ma; Shi-Gui Li; Hai-Lei Wei; Xiao-Xia Zhang (Current Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The role of sulfur cycle in new particle formation: Cycloaddition reaction of SO3 to H2S - Haijie Zhang; Wei Wang; Liang Fan; Junling Li; Yanqin Ren; Hong Li; Rui Gao; Yisheng Xu (Journal of Environmental Sciences, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Edible nonaqueous foams: Recent advances in the formation, stabilization, characterization, and applications - Xin Hong; Liuping Fan; Jinwei Li (Food Chemistry, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Leaching kinetics combined with DFT simulation to explore the mechanism of differential phase transformation of calcium in magnesium slag induced by HCl and the preparation of calcium carbonate by electrolytic carbonization - Ren-yun Zhang; Yan Liu; Zhi-yu Fan; Ji-dong Li; Yi-yong Wang; Ting-an Zhang; Hong-xuan Xing; Yi-feng Liu; Xue-qiang Gong (Chemical Engineering Journal, 2025)

Application of green manure combined with synthetic nitrogen fertilizer enhances soil aggregate stability in an arid wheat cropping system - Guocui Wang; Hanting Li; Falong Hu; Wen Yin; Zhilong Fan; Hong Fan; Yali Sun; Wei He; Qiang Chai (Applied Soil Ecology, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Outdoor light at night exposure was associated with hypothyroidism in pregnant women: A national study in China - Hong-Xing Zou; Li-Wen Hu; Zheng Zhang; Alexander E.P. Heazell; Xueran Wang; Wentao Yue; Xiao-Fan Lu; Xiao-Yi Liu; Shuo Zhang; Le-Bing Wang; Enjie Zhang; Shaofei Su; et al. (Science of The Total Environment, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

3D hot spot construction on the hydrophobic interface with SERS tags for quantitative detection of pesticide residues on food surface - Yan-Hui Wang; Chen Huang; Xiao Wu; Xiao-Feng Liu; En-Ming You; Sheng-Hong Liu; An Wang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Influence of view factors on outdoor thermal comfort of residential areas in hot-humid regions - Li Li; Jiayi Hong; Mingtao Ma; Chengliang Fan; Xiu Xiong; Yue Pang (International Journal of Biometeorology, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Potassium status and the risk of type 2 diabetes, cardiovascular diseases, and mortality: a meta-analysis of prospective observational studies - Yahui Fan; Min Wu; Lu Ding; Huixin Ji; Jinping Zhao; Xiaohui Li; Zhaofang Li; Sijiao Liu; Hong Jiang; Jia Shi; Haoyuan Lei; Mingxu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Strain-level multidrug-resistant pathogenic bacteria in urban wastewater treatment plants: Transmission, source tracking and evolution - Yanmei Zhao; Lu Fan; Shu-Hong Gao; Fang Huang; Zelin Lei; Wenxiu Wang; Rui Gao; Zihan Dai; Qian Li; Bin Liang; Aijie Wang (Water Research, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Molecular-level insights into the brewing-dependent chemical diversity, properties, and formation mechanism of Moutai Base baijiu using Fourier transform ion cyclotron resonance mass spectrometry - Yuhan Cao; Yubo Yang; Bohan Zhang; Fanhao Song; Lizhang Yang; Hong Chang; Fan Yang; Xiaoli Zhao; Huabin Tu; Li Wang; Fengchang Wu (Food Chemistry, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Exceptional heatwaves and mortality in Europe: Greater impacts since the coronavirus disease 2019 outbreak - Zhiwei Li; Yinguang Fan; Zhiwei Xu; Hung Chak Ho; Shilu Tong; Cunrui Huang; Zhongliang Bai; Yiming Gai; Wenjun Cheng; Jihong Hu; Yufan Feng; Hao Zheng; et al. (Environmental Pollution, 2024)

Analysis of landslide deformation mechanisms and coupling effects under rainfall and reservoir water level effects - Boyi Li; Guilin Wang; LiChuan Chen; Fan Sun; Runqiu Wang; MingYong Liao; Hong Xu; Siyu Li; Yanfei Kang (Engineering Geology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

A high-permeability method for extracting purple yam saponins based on ultrasonic-assisted natural deep eutectic solvent - Yu-Jiao Hou; Peng-wei Wang; Han Zhang; Ying-Ying Fan; Xu Cao; Yan-Qiong Luo; Qian Li; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Alleviative effects of C60 fullerene nanoparticles on arsenate transformation and toxicity to Danio rerio - Xiaoyan Wang; Zhaomin Dong; Qing Zhao; Chengwei Li; Wen-Hong Fan (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Theoretical and experimental insights into the effects of CO2 on the heterogeneous NO reduction over char surface: Gasification and CO2-mediated oxygen rearrangement - Ji Liu; Yuan-gu Xia; Meng-fan Liu; Bin Hu; Hong-jin Zhang; Ji-hong Li; Zhen-xi Zhang; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

Evaluation of four novel non-grain protein sources completely replacing soybean meal on growth performance, serum biochemistry, amino acid transport and intestinal health of grass carp (Ctenopharyngodon idella) at different water temperatures - Di Wu; Ze Fan; Xianhu Zheng; Jinnan Li; Meng Zhou; Haitao Zhang; Hong Xu; Shouqi Xie; Liansheng Wang (Fish & Shellfish Immunology, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Accurate model development for predicting sprinkler water distribution on undulating and mountainous terrain - Fan Yang; Yue Jiang; Hong Li; Xin Hui; Shouchen Xing (Computers and Electronics in Agriculture, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

Synergistic degradation of 2,4-dichlorophenoxyacetic acid in water by interfacial pre-reduction enhanced peroxymonosulfate activation derived from novel zero-valent iron/biochar - Yatao Liu; Tianyi Wang; Qiaofeng Hong; Chen Li; Zhenbei Wang; Fan Li; Mingyuan Li; Mengfei He; Fei Qi; Ewa Maria Siedlecka; Jolanta Kumirska (Journal of Hazardous Materials, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Does the morphology of residential greenspaces contribute to the development of a cardiovascular-healthy city? - Rubing Pan; Weiqiang Wang; Ning Wei; Li Liu; Weizhuo Yi; Jian Song; Jian Cheng; Hong Su; Yinguang Fan (Environmental Research, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

The observation of atmospheric HONO by wet-rotating-denuder ion chromatograph in a coastal city: Performance and influencing factors - Baoye Hu; Yue Wang; Jinsheng Chen; Naihua Chen; Youwei Hong; Lingling Xu; Xiaolong Fan; Mengren Li; Lei Tong (Environmental Pollution, 2024)

Improving crop productivity by optimizing straw returning patterns to delay senescence of wheat leaves - Pan Li; Wen Yin; Zhilong Fan; Falong Hu; Lianhao Zhao; Hong Fan; Wei He; Qiang Chai (European Journal of Agronomy, 2024)

Spray of water-in-oil emulsified heavy oil with high water content - Ruo-Fan Shi; Yu-Feng Xi; Li-Tao Wang; Hong-Jun Lu; Xiao Zhang; Xin-Yue Zhang; Zi-Bin Huang; Pei-Qing Yuan (Chemical Engineering Journal, 2024)

Structures of multiple states of the nicotinamide nucleotide transhydrogenase from Escherichia coli - Jiao Li; Sangjin Hong; Xiuxiu Ma; Fangling Xu; Quan Li; Fan Wang; Kai Zhang; Robert B. Gennis; Jiapeng Zhu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Structure and mechanism of the energy-coupled nicotinamide nucleotide transhydrogenase from E. Coli - Robert B. Gennis; Jiao Li; Sangin Hong; Xiuxiu Ma; Fangling Xu; Quan Li; Fan Wang; Kai Zhang; Jiapeng Zhu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Selenium Deficiency Can Promote the Expression of VEGF and Inflammatory Factors in Cartilage Differentiation and Mediates Cartilage Injury - Xiang Meng; Xiumei Meng; Zeju He; Ye Yuan; Yong Fan; Li Yin; Yu Tong; Zheping Hong; Senbo Zhu; Qiong Zhang; Qing Bi (Biological Trace Element Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Hipposponols A and B, two new 9, 11-secosterols from the marine sponge Hippospongia lachne de Laubenfels - Ya-Fang Ding; Li-Yun Liu; Jie Tang; Dong-Xue Fan; Yuan-Yuan Ji; Hou-Wen Lin; Jie Wang; Li-Li Hong (Natural Product Research, 2024)

Temperature dependence of the rain-gas and snow-gas partition coefficients for nearly a thousand chemicals - Pu-Fei Yang; Wan-Li Ma; Hang Xiao; Kaj M. Hansen; Liang Wang; Jing-Jing Sun; Li-Yan Liu; Zi-Feng Zhang; Hong-Liang Jia; Yi-Fan Li (Chemosphere, 2024)

Serum miR-192–5p is a promising biomarker for lethal radiation injury - Meng Jia; Zhanyu Wang; Xin Liu; Hong Zhang; Ying Fan; Dan Cai; Yaqiong Li; Liping Shen; Zhidong Wang; Qi Wang; Zhenhua Qi (Toxicology Letters, 2024)

Fabrication of high mechanical strength and high porosity PVDF isoporous membranes based on inverse opal photonic crystals - Sha Fan; Yu Wang; Xinyi Hong; Gaofeng Liu; Chengcai Li; Hailin Zhu; Bin Yu; Guojin Liu (Journal of Water Process Engineering, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

An efficient microwave-assisted method using ethyl lactate/water cosolvent for lignocellulosic biomass fractionation - Na Wang; Kai Liu; Anran Xu; Hong Li; Zhenyu Zhao; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Ucf-101 alleviates Ischaemia/Reperfusion induced retinal inflammation and injury via suppressing oxidative damage - Yuan-Jun Qin; Guangyi Huang; Jing Liao; Li Jiang; Fen Tang; Ningning Tang; Yiyi Hong; Chaolan Shen; Qianqian Lan; Fan Xu; Lifei Chen (Journal of Molecular Histology, 2024)

Glaesserella parasuis serotype 5 induces pyroptosis via the RIG-I/MAVS/NLRP3 pathway in swine tracheal epithelial cells - Yuhui Li; Mengru Guo; Qing Wang; Hong Zhou; Wenda Wu; Huixing Lin; Hongjie Fan (Veterinary Microbiology, 2024)

Quantitative reconstruction of a single super rainstorm using daily resolved δ18O of land snail shells - Guozhen Wang; Jibao Dong; Tao Han; Chengcheng Liu; Fan Luo; Haotian Yang; Miaohong He; Guoqiang Tang; Nanyu Zhao; Qian Zhang; Gang Xue; John Dodson; et al. (Science Bulletin, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

An alkali-extracted neutral heteropolysaccharide from Phellinus nigricans used as an immunopotentiator in immunosuppressed mice by activating macrophages - Feihe Wang; Na Li; Hong Li; Yao Di; Fan Li; Peng Jiang; Guiyun Wang (Carbohydrate Polymers, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Constructing extrinsic oxygen vacancy on the surface of photocatalyst as CO2 and electrons reservoirs to improve photocatalytic CO2 reduction activity - Zaiyong Jiang; Hao Li; Zhimin Yuan; Zheng Wang; Maohong Fan; Wenkang Miao; Hong He (Journal of Environmental Sciences, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Study of the antivirus function mediated by STING in Micropterus salmoides - Jin-Quan Fan; Qian-Ming Hong; Li-Shi Liu; Qi Chen; Yi-Hong Chen (Fish & Shellfish Immunology, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Analysis of morphology, histology characteristics, and circadian clock gene expression of Onychostoma macrolepis at the overwintering period and the breeding period - Yibin Ding; Jincan Li; Yao Gao; Xiaolin Wang; Yang Wang; Chao Zhu; Qimin Liu; Lijuan Zheng; Meng Qi; Lijun Zhang; Hong Ji; Fangxia Yang; et al. (Fish Physiology and Biochemistry, 2024)

Modulation and Enhancement of Red Luminescence in Ca2GdSbO6: Eu3+ Phosphor by Co-Doping with Bi3+ - Jing Li; Junhuang Hong; Yingchao Xu; Yue Liu; Haoshuang Fan (Journal of Fluorescence, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Nutrient runoff and leaching under various fertilizer treatments and pedogeographic conditions: A case study in tobacco (Nicotiana tabacum L.) fields of the Erhai Lake basin, China - Chen Wang; Qi Miao; Zhibiao Wei; Yingxin Guo; Junying Li; Zhiyong Fan; Yanxia Hu; Hong Zhang; Junwei Sun; Zhenling Cui (European Journal of Agronomy, 2024)

Photochemical pollution during summertime in a coastal city of Southeast China: Ozone formation and influencing factors - Gaojie Chen; Xiaoting Ji; Jinsheng Chen; Lingling Xu; Baoye Hu; Ziyi Lin; Xiaolong Fan; Mengren Li; Youwei Hong; Jinfang Chen (Atmospheric Research, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Sources appointment and health risks of PM2.5-bound trace elements in a coastal city of southeastern China - Ziyi Lin; Xiaolong Fan; Gaojie Chen; Youwei Hong; Mengren Li; Lingling Xu; Baoye Hu; Chen Yang; Yanting Chen; Zhiqian Shao; Jinsheng Chen (Journal of Environmental Sciences, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

LRRK2 is involved in heat exposure-induced acute lung injury and alveolar type II epithelial cell dysfunction - Yindan Wang; Wenjun Fan; Guoqing Zhang; Lisha Zhao; Ting Li; Lu Zhang; Tong Hou; Huihua Hong; Zhenqiang You; Qinghua Sun; Ran Li; Cuiqing Liu (Environmental Pollution, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Meteorological impacts on the unexpected ozone pollution in coastal cities of China during the unprecedented hot summer of 2022 - Xiaoting Ji; Gaojie Chen; Jinsheng Chen; Lingling Xu; Ziyi Lin; Keran Zhang; Xiaolong Fan; Mengren Li; Fuwang Zhang; Hong Wang; Zhi Huang; Youwei Hong (Science of The Total Environment, 2024)

Single-cell transcriptome landscape of zebrafish liver reveals hepatocytes and immune cell interactions in understanding nonalcoholic fatty liver disease - Yingyi Huang; Xiang Liu; Hong-Yan Wang; Jian-Yang Chen; Xianghui Zhang; Yubang Li; Yifang Lu; Zhongdian Dong; Kaiqiang Liu; Zhongduo Wang; Qian Wang; Guangyi Fan; et al. (Fish & Shellfish Immunology, 2024)

Physiological responses of low- and high-cadmium accumulating Robinia pseudoacacia-rhizobium symbioses to cadmium stress - Lan Gao; Shufeng Wang; Dongchen Zou; Xu Fan; Pan Guo; Hongxia Du; Wancang Zhao; Qiaozhi Mao; Hong Li; Ming Ma; Heinz Rennenberg (Environmental Pollution, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Atmospheric oxidation capacity and O3 formation in a coastal city of southeast China: Results from simulation based on four-season observation - Gaojie Chen; Taotao Liu; Jinsheng Chen; Lingling Xu; Baoye Hu; Chen Yang; Xiaolong Fan; Mengren Li; Youwei Hong; Xiaoting Ji; Jinfang Chen; Fuwang Zhang (Journal of Environmental Sciences, 2024)

Molecular characterization and functional study of a galectin-9 from a teleost fish, Boleophthalmus pectinirostris - Yong-Fei Zhu; Yi-Fan Hu; Chang-Hong Li; Li Nie; Jiong Chen (Fish & Shellfish Immunology, 2024)

Giant electrical conductivity difference enabled liquid metal-hydrogel hybrid printed circuits for soft bioelectronics - Caicai Jiao; Liangtao Li; Baoyang Lu; Qian Wang; Weili Hong; Xing Chen; Lingqian Chang; Xinpeng Wang; Yang Wang; Kang Sun; Liang Hu; Yubo Fan (Chemical Engineering Journal, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Porcine circovirus type 2 and Glaesserella parasuis serotype 4 co-infection activates Snail1 to disrupt the intercellular junctions and facilitate bacteria translocation across the tracheal epithelium - Mengru Guo; Jianan Zhang; Qing Wang; Jinsheng Tang; Yuhui Li; Hong Zhou; Huixing Lin; Zhe Ma; Hongjie Fan (Veterinary Microbiology, 2024)

Enhancing urban real-time PM2.5 monitoring in street canyons by machine learning and computer vision technology - Zhiguang Fan; Yuan Zhao; Baicheng Hu; Li Wang; Yuxuan Guo; Zhiyuan Tang; Junwen Tang; Jianmin Ma; Hong Gao; Tao Huang; Xiaoxuan Mao (Sustainable Cities and Society, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Sequential usage of charged polyacrylamide for positive feedback in enhancing dewaterability of dredged sediment - Qingbo Zhang; Misha Liu; Jifu Yin; Chenwei Yuan; Xiaodan Mao; Guojun Hong; Yu Wang; Fan Yang; Fengting Li; Jie Li (Journal of Water Process Engineering, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Ultrasensitive two-photon probes for rapid detection of β-galactosidase during fruit softening and cellular senescence - Yi-Min Shan; Kang-Kang Yu; Fan-Yuan Yu; Yan-Hong Liu; Xiao-Qi Yu; Kun Li (Food Chemistry, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Moderate altitude exposure impacts host fasting blood glucose and serum metabolome by regulation of the intestinal flora - Dan Liu; Xiaoyan Gao; Xiaoran Huang; Yanqun Fan; Yu-E Wang; Yuelin Zhang; Xuanfu Chen; Jielu Wen; Haiwei He; Yimei Hong; Ying Liang; Yuxiao Zhang; et al. (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Enhanced inactivation of Microcystis aeruginosa by heterogeneous interfacial Ag2MoO4/TACN under visible light - Gongduan Fan; Xinyi Wu; Yang Tao; Mingqian Xia; Zhuoyi Chen; Hao Li; Jing Luo; Jianyong Zou; Zhanglin Hong; Kaiqin Xu (Journal of Water Process Engineering, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Inhibition of hyperpolarization-activated cyclic nucleotide-gated cation channel attenuates cerebral ischemia reperfusion-induced impairment of learning and memory by regulating apoptotic pathway - Zhi He; Jue Liu; Xiao-Li Zeng; Jing-Hong Fan; Ke Wang; Yue Chen; Zi-Cheng Li; Bo Zhao (Metabolic Brain Disease, 2023)

Exploring environmental obesogenous effects of organic ultraviolet filters on children from a case-control study - Beili Wang; Yihui Jin; Juan Li; Fan Yang; Hong Lu; Jinyang Zhou; Shijian Liu; Zhemin Shen; Xiaodan Yu; Tao Yuan (Chemosphere, 2023)

Long-term exposure to ambient fine particulate matter-bound polycyclic aromatic hydrocarbons and cancer mortality: A difference-in-differences approach - Yingxin Li; Zhaoyu Fan; Wenfeng Lu; Ruijun Xu; Tingting Liu; Likun Liu; Gongbo Chen; Ziquan Lv; Suli Huang; Yun Zhou; Yuewei Liu; Hong Sun (Chemosphere, 2023)

Photochemistry in the urban agglomeration along the coastline of southeastern China: Pollution mechanism and control implication - Gaojie Chen; Qiao Shi; Lingling Xu; Shaocai Yu; Ziyi Lin; Xiaoting Ji; Xiaolong Fan; Youwei Hong; Mengren Li; Fuwang Zhang; Jinfang Chen; Jinsheng Chen (Science of The Total Environment, 2023)

The potential role of subseafloor fungi in driving the biogeochemical cycle of nitrogen under anaerobic conditions - Jun-Peng Jiang; Shuang Leng; Yi-Fan Liao; Xuan Liu; Dong-Xu Li; Chen Chu; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2023)

Peracetic acid combined with ultraviolet for ibuprofen degradation: Activation mechanism and reactive species contribution - Gongduan Fan; Yujian Li; Banghao Du; Lei Yao; Chenjian Cai; Hao Li; Shoubin Chen; Jianyong Zou; Zhanglin Hong; Kai-Qin Xu (Process Safety and Environmental Protection, 2023)

Heteropoly acid supported on hierarchical Y zeolite decorated SiC foam as the structured catalytic packing for reactive distillation synthesis of ethyl lactate - Qiuyan Ding; Hengyu Shen; Zongliang Kou; Hong Li; Xiaolei Fan; Xiaoxia Ou; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2023)

Perturbation and mechanism of non-antibiotic drug in regulating resistome and metabolome of anammox consortia: An overlooked and underrated cause of multiresistance - Qian Wu; Xin Wang; Hong-Yan Li; Dong-Qi Huang; Bao-Cheng Huang; Ren-Cun Jin; Nian-Si Fan (Chemical Engineering Journal, 2023)

USP22 knockdown protects against cerebral ischemia/reperfusion injury via destabilizing PTEN protein and activating the mTOR/TFEB pathway - Yanling Li; Jing Gao; Chuntian Liu; Ning Bu; Shuqin Zhan; Haiqin Wu; Ru Zhang; Hong Sun; Hong Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Fate of 15N-labelled urea as affected by long-term manure substitution - Fuyue Dai; Bingqian Fan; Jungai Li; Yitao Zhang; Hongyuan Wang; Zhen Wang; Muhammad Amjad Bashir; Golnaz Ezzati; Limei Zhai; Hong J. Di; Hongbin Liu (Science of The Total Environment, 2023)

Highly efficient S-scheme AgBr/BiOBr with visible light photocatalytic performance for carbamazepine degradation: Mechanism insight and toxicity assessment - Gongduan Fan; Kaiwei Hu; Xia Li; Mingqian Xia; Zhuoyi Chen; Shoubin Chen; Jing Luo; Jianyong Zou; Zhanglin Hong; Kaiqin Xu (Journal of Environmental Chemical Engineering, 2023)

Cytological observations in abortion formation and morphological character of pollen in seedless chestnut rose (Rosa sterilis) - Qian Du; Kui Zhou; Siling Zhong; Changying Li; Jinbu Fan; Qian Wang; Yi Hong; Xiaopeng Wen (Flora, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Molybdenum cycling in Andean-type subduction and metallogenic implications - Wei Mao; Hong Zhong; Jiehua Yang; Liang Liu; Yazhou Fu; Xingchun Zhang; Jie Li; Le Zhang; Haifeng Fan; Yanwen Tang; Xiaocui Chen (Mineralium Deposita, 2023)

Simultaneous detection of multiple influenza virus subtypes based on microbead-encoded microfluidic chip - Shao-Li Hong; Xuan Wang; Zhong-Hua Bao; Meng-Fan Zhang; Man Tang; Nangang Zhang; Huihong Liu; Zi-Yuan Zhu; Kan Liu; Zhi-Liang Chen; Wei Li (Analytica Chimica Acta, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

The effect of nitrous acid (HONO) on ozone formation during pollution episodes in southeastern China: Results from model improvement and mechanism insights - Baoye Hu; Gaojie Chen; Jinsheng Chen; Lingling Xu; Xiaolong Fan; Youwei Hong; Mengren Li; Ziyi Lin; Mingqiang Huang; Fuwang Zhang; Hong Wang (Science of The Total Environment, 2023)

A generalized land surface reflectance reconstruction method for aerosol retrieval: Application to the Particulate Observing Scanning Polarimeter (POSP) onboard GaoFen-5 (02) satellite - Zheng Shi; Yisong Xie; Zhengqiang Li; Ying Zhang; Cheng Chen; Linlu Mei; Hua Xu; Haofei Wang; Yang Zheng; Zhenhai Liu; Jin Hong; Mengyao Zhu; et al. (Remote Sensing of Environment, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Pilot-scale study on an advanced Fe-Cu process for refractory wastewater pretreatment - Jin-Hong Fan; Zhen-long Yao; De-li Wu; Xia Liu; Lu-ming Ma (Journal of Hazardous Materials, 2023)

Carbon footprints in pork production and consumption in China from 2005 to 2020 - Haoyue Fan; Kaijie Chen; Haibo Ma; Jian He; Hongyu Li; Zhaoli Yang; Qingyi Wu; Chengsi Zhang; Shulian Zhang; Tao Huang; Hong Gao; Jianmin Ma (Journal of Cleaner Production, 2023)

A sublethal dose of neonicotinoid imidacloprid precisely sensed and detoxified by a C-minus odorant-binding protein 17 highly expressed in the legs of Apis cerana - Yi-Lei Qiu; Fan Wu; Li Zhang; Hu-Qiang Jiang; Jin-Tao Chen; Ying-Jia Pan; Hong-Liang Li (Science of The Total Environment, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Pathogens identification and resistance evaluation on bacterial canker in Actinidia arguta germplasm - Hong Y. Qin; Ying Zhao; Xiu L. Chen; Bao X. Zhang; Xin Wen; Chang Y. Li; Shu T. Fan; Yue Wang; Yi M. Yang; Pei L. Xu; Ying X. Liu; Jun Ai (Journal of Plant Pathology, 2023)
Pathogen isolation and identification were performed on Actinidia arguta ‘Longcheng No. 2’ occurring bacterial canker from Liaoning Province, China. The pathogenic bacteria were identified as Pseudomonas syringae pv. actinidiae (Psa) by the analysis of morphology,16S rRNA and gyrB sequence, which were identified as Psa biovar 2 by Psa-specific primer sequence analysis. The pathogenicity tests were carried out with the isolate ‘R12’ and type strain ‘M228’ (biovar 3) as a control; the results showed that the phloem of green stems in A. arguta ‘Kuilv’ could be infect rapidly by R12, and milky mucus flowed from wounds, then the phloem turned black-brown, but it had strong resistance to Psa M228. In order to evaluate the resistance on Psa R12, 54 A. arguta germplasm resources were infected by artificial inoculation of stems, with A. deliciosa cv. ‘Hongyang’ and A. chinensis cv. ‘Xuxiang’, as control plant material, and their resistance levels were classified according to the disease index. The 54 tested materials exhibited differences in resistance to Psa R12, but no immune materials were found. In general, the germplasms were divided into five disease resistance categories, including 2 accessions with high resistance ‘Jianfengkuilv’ and ‘TL20013’, accounted for 3.70% of all the inoculated accessions; there were 11 resistant accessions, 15 tolerant accessions, 21 susceptible accessions, 5 highly susceptible accessions among them, accounted for 20.37%, 27.78%, 38.89% and 9.26%, respectively. In this study, the screening of disease-resistant germplasms could lay a foundation for further research on gene mapping, resistance mechanisms and breeding-resistant varieties of A. arguta to Psa.

Compound impact of COVID-19, economy and climate on the spatial distribution of global agriculture and food security - Peiwen Yao; Hong Fan; Qilong Wu; Jiani Ouyang; Kairui Li (Science of The Total Environment, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Forecasting residential electricity consumption using the novel hybrid model - Guo-Feng Fan; Ya Zheng; Wen-Jing Gao; Li-Ling Peng; Yi-Hsuan Yeh; Wei-Chiang Hong (Energy and Buildings, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

Seasonal variation of aerosol optical properties in a coastal city of southeast China: Based on one year of measurements - Lingjun Li; Mengren Li; Siqing Zhang; Liqian Yin; Xiaoting Ji; Yuping Chen; Chao Dong; Lingling Xu; Xiaolong Fan; Gaojie Chen; Ziyi Lin; Youwei Hong; et al. (Atmospheric Environment, 2023)

Evaluation of the treatment effect of rear slope cutting on hydrodynamic pressure landslides: A case study - Li Wang; Jun-jie Huang; Yong Chen; Shi-mei Wang; Zhi-hong Fan; Fei Guo; Xiao-wei Li (Journal of Mountain Science, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

α-Synuclein Induced the Occurrence of RBD via Interaction with OX1R and Modulated Its Degradation - Jing Kai Fan; Meng Chen Wang; Hui Min Yang; Jian Nan Zhang; Li Gu; Hong Zhang (NeuroMolecular Medicine, 2023)

Mechanisms controlling the transport and evaporation of human exhaled respiratory droplets containing the severe acute respiratory syndrome coronavirus: a review - Leslie Kojo Norvihoho; Jing Yin; Zhi-Fu Zhou; Jie Han; Bin Chen; Li-Hong Fan; Eric Lichtfouse (Environmental Chemistry Letters, 2023)

Assessment of the establishment success of surfgrass Phyllospadix iwatensis from shoots in a leaf trimming method: implications for large-scale restoration - Jie Sun; Fan-Shu Luo; Guo-Xu Yu; Hong-Yu Zhang; Wen-Tao Li; Pei-Dong Zhang (Frontiers in Marine Science, 2023)
Phyllospadix spp. play a crucial role in the supply of ecosystem services in rocky shores, but they have been rapidly reduced because of natural and anthropogenic causes. Since Phyllospadix spp. are attached to rocks in the surf zone with a strong hydrodynamic condition, their transplanted shoots easily disappear due to the high current velocity, resulting in the failure of transplantation. We described a leaf trimming method for transplanting shoots of surfgrass Phyllospadix iwatensis and evaluated the method’s establishment success for potential use in large-scale restoration projects. A 30-day laboratory experiment was conducted to determine the effect of leaf trimming on shoot survival, growth, and physiology. Successful establishment of new patches from shoots transplanted with the leaf trimming method was assessed through a shoot-transplanting field experiment over 15 months. The survival of P. iwatensis shoots was not significantly affected by the leaf trimming proportion of 10%–60%. The leaf elongation rate and total leaf area of the shoots exposed to 10%–50% leaf trimming reached or exceeded those of the control at the end of the laboratory experiment; however, the growth of the shoots under 60% leaf trimming was significantly lower than those under the control ( p < 0.05). The soluble sugar and starch contents of the shoots also displayed a similar trend to the growth, with the lowest values attained at 60% of leaf trimming. The survival rate of shoots exposed to 50% leaf trimming treatment was 70% after 15 months following transplantation, which was 1.23 times higher than that of shoots in the control ( p < 0.05). The shoot height in the 50% leaf trimming treatment was 1.02 times higher than that of shoots in the control at the end of the field experiment. There were no significant differences in photosynthetic pigment contents of P. iwatensis shoots between the leaf trimming treatment and the control ( p > 0.05). Our study suggested that the leaf trimming method is an efficient restoration technique for the transplantation of P. iwatensis shoots, and is potentially useful in facilitating large-scale restoration projects.

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Dietary aromatase inhibitor treatment converts XY gsdf homozygous mutants to sub-fertile male in Nile tilapia (Oreochromis niloticus) - Sen Fan; Hong-Juan Shi; You-Xing Peng; Yuan-Qing Huang; Mou-Yan Jiang; Guang-Li Li; De-Shou Wang; Dong-Neng Jiang (Aquaculture, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

La2Ti2O7 nanosheets modified by Pt quantum dots for efficient NO removal avoiding NO2 secondary pollutant - Li Lv; Hong-Dan Yang; Qi-Wen Chen; Huiqing Fan; Jian-Ping Zhou (Environmental Research, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Versatility of Sb-doping enabling argyrodite electrolyte with superior moisture stability and Li metal compatibility towards practical all-solid-state Li metal batteries - Hong Liu; Qisi Zhu; Yuhao Liang; Chao Wang; Dabing Li; Xiaoxue Zhao; Lei Gao; Li-Zhen Fan (Chemical Engineering Journal, 2023)

Variations of chemical composition of NR-PM1 under the influence of sea land breeze in a coastal city of Southeast China - Yuping Chen; Chen Yang; Lingling Xu; Xiaolong Fan; Jiayan Shi; Ronghua Zheng; Youwei Hong; Mengren Li; Taotao Liu; Gaojie Chen; Liqian Yin; Jinsheng Chen (Atmospheric Research, 2023)

Beneficial effects of red and blue light on potato leaf antioxidant capacity and tuber bulking - Wei He; Qiang Chai; Dan Zhang; Wenli Li; Cai Zhao; Wen Yin; Hong Fan; Aizhong Yu; Falong Hu; Zhilong Fan (Physiology and Molecular Biology of Plants, 2023)

Ioversol Induced Microglia Proinflammatory Activation and Oxidative Stress in Rats - Tao Li; Lili Zhao; Hong Fan; Zhiyang Chen; Ye Li; Meijuan Dang; Ziwei Lu; Jialiang Lu; Qiao Huang; Heying Wang; Shengxi Wu; Guilian Zhang; et al. (Neurotoxicity Research, 2023)

Design, synthesis and fungicidal evaluation of novel psoralen derivatives containing sulfonohydrazide or acylthiourea moiety - Jingyue Dong; Kun Li; Zeyu Hong; Lei Chen; Liangfu Tang; Lijun Han; Lai Chen; Zhijin Fan (Molecular Diversity, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Gli2-induced lncRNA Peg13 alleviates cerebral ischemia-reperfusion injury by suppressing Yy1 transcription in a PRC2 complex-dependent manner - Yanling Li; Chuntian Liu; Hong Fan; Yun Du; Ru Zhang; Shuqin Zhan; Guilian Zhang; Ning Bu (Metabolic Brain Disease, 2023)

Genome-wide investigation of the WRKY transcription factor gene family in weeping forsythia: expression profile and cold and drought stress responses - Ya-Lin Yang; Samuel A. Cushman; Shu-Chen Wang; Fan Wang; Qian Li; Hong-Li Liu; Yong Li (Genetica, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

Impact of A/B-type wheat starch granule ratio on rehydration behavior and cooking quality of noodles and the underlying mechanisms - Jiaying Shang; Bo Zhao; Limin Li; Mei Liu; Jing Hong; Xiangqi Fan; Tengfei Wu; Chong Liu; Xueling Zheng (Food Chemistry, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Host's P85α genotype restructures the gut microbiota and regulates fat metabolism in gibel carp - Tengba Fan; Ivan Jakovlić; Qiyong Lou; Dong Han; Wenxiang Li; Ming Li; Hong Zou; Guitang Wang; Shangong Wu (Aquaculture, 2023)

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Amorphous SnO2 decorated ZnSn(OH)6 promotes interfacial hydroxyl polarization for deep photocatalytic toluene mineralization - Lvcun Chen; Kanglu Li; Yan Yang; Ting Xue; Hong Wang; Ben Lei; Jianping Sheng; Fan Dong; Yanjuan Sun (Journal of Hazardous Materials, 2023)

Unsupervised classification of polarimetric SAR images via SV G p 0 MM with extended variational inference - Ze-Chen Li; Heng-Chao Li; Gui Gao; Ze-Xi Hua; Fan Zhang; Wen Hong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of concentration of nickel precursor on the synthesis of Ni phyllosilicate for CO2 methanation: The promotion of supersaturation - Qinzhen Fan; Hai Li; Hong Chen; Lihua Cheng; Qing Liu (Fuel, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

A robust protein-peptide co-assembling nanoformulation (PePCAN) platform with significant cell-entry characteristics for targeted cancer therapy - Xiaoyuan Zhao; Xiang Li; Bo Li; Yao Sun; Yejiao Shi; Huaxing Shen; Fan Wang; Jingjing Li; Farukh Sharopov; Zainiddin Mukhiddinov; Chao Ma; Kai Liu; et al. (Chemical Engineering Journal, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Charge instability of topological Fermi arcs in chiral crystal CoSi - Zhicheng Rao; Quanxin Hu; Shangjie Tian; Qing Qu; Congrun Chen; Shunye Gao; Zhenyu Yuan; Cenyao Tang; Wenhui Fan; Jierui Huang; Yaobo Huang; Li Wang; et al. (Science Bulletin, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

Impact of salt and homogenization on yield, aggregation, and mechanical characteristics of wheat gluten separated by batter procedure - Xiangqi Fan; Chong Liu; Limin Li; Jiaying Shang; Jing Hong; Mei Liu; Xueling Zheng (Journal of Cereal Science, 2023)

Freeze-thaw stability and rheological properties of high internal phase emulsions stabilized by phosphorylated perilla protein isolate: Effect of tea saponin concentration - Qiaoli Zhao; Xin Hong; Liuping Fan; Yuanfa Liu; Jinwei Li (Food Hydrocolloids, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Spraying EPDM@NPs as an efficient strategy for polyethylene-based high-voltage insulation - Fan-Bo Meng; Xiangrong Chen; Yiwen Shi; Zelin Hong; Hanshan Zhu; Awais Muhammad; Hao Li; Ashish Paramane (Chemical Engineering Journal, 2023)

Land subsidence calculation model under the coupling effect of groundwater and coal mining - Yiguo Xue; Hong Chen; Fanmeng Kong; Zhiqiang Li; Daohong Qiu; Qiqi Chen; Fan Yang; Xudong Jiang (Earth Science Informatics, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

The development of SSR markers from the endangered plant Tetracentron sinense Oliv. (Tetracentraceae) based on RAD–seq technique - Zhong–Qiong Tian; Fan Duan; Shan Li; Xiao-Hong Gan (Biologia, 2022)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

First report of Claviceps purpurea causing ergot disease on wheat (Triticum aestivum) in southwestern China - Mingliang Ding; Zhiqin Wang; Qi Fan; Hefa Liao; Kun Liu; Mingju Li; Zhanhong Ma; Hong Yu; Yuanbing Wang (Journal of Plant Pathology, 2022)

Ketamine induces rapid antidepressant effects via the autophagy-NLRP3 inflammasome pathway - Dongbin Lyu; Fan Wang; Mengke Zhang; Weichieh Yang; Haijing Huang; Qinte Huang; Chenglin Wu; Nuoshi Qian; Meiti Wang; Huanfei Zhang; Sichai Zheng; Jing Chen; et al. (Psychopharmacology, 2022)

Responses of absorptive root and mycorrhizal colonization of Chinese fir (Cunninghamia lanceolata) to varied environmental conditions - Ying-Chun Liao; Hou-Bao Fan; Liang Li; Xiao-Hua Wei; Hui-Min Wang; Hong-Lang Duan; Wen-Fei Liu; Jia-Li Liu (Plant Ecology, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Astrocyte Activation, but not Microglia, Is Associated with the Experimental Mouse Model of Schizophrenia Induced by Chronic Ketamine - Ying Wei; Li Xiao; Weihao Fan; Jing Zou; Hong Yang; Bo Liu; Yi Ye; Di Wen; Linchuan Liao (Journal of Molecular Neuroscience, 2022)

Can collaborative innovation constrain ecological footprint? Empirical evidence from Guangdong-Hong Kong-Macao Greater Bay Area, China - Xiaojun You; Qixiang Li; Kyle M. Monahan; Fei Fan; Haiqian Ke; Na Hong (Environmental Science and Pollution Research, 2022)

Design and mechanism of photocatalytic oxidation for the removal of air pollutants: a review - Kanglu Li; Hong Wang; Jianjun Li; Fan Dong (Environmental Chemistry Letters, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

History of suicide attempts associated with the thinning right superior temporal gyrus among individuals with schizophrenia - Yi Yin; Jinghui Tong; Junchao Huang; Baopeng Tian; Song Chen; Shuping Tan; Zhiren Wang; Fude Yang; Yongsheng Tong; Fengmei Fan; Peter Kochunov; Neda Jahanshad; et al. (Brain Imaging and Behavior, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Vermicompost Application Enhances Halophyte Suaeda salsa Performance and Improves Coastal Saline Soil Quality - Jing-Fang Cai; Xuan-Shao Liu; Kai Sun; Fan Jiang; Ming-Xiang Zhang; Hong-Li Li; Fei-Hai Yu (Journal of Soil Science and Plant Nutrition, 2022)

Association between exposure to ambient air pollution and semen quality in adults: a meta-analysis - Hong Qian; Qiaoqiao Xu; Wenkai Yan; Yun Fan; Zhi Li; Chengzhe Tao; Feng Zhang; Chuncheng Lu (Environmental Science and Pollution Research, 2022)

SYL3-k increases style length and yield of F1 seeds via enhancement of endogenous GA4 content in Oryza sativa L. pistils - Xiaojing Dang; Yuanqing Zhang; Yulong Li; Siqi Chen; Erbao Liu; Bingjie Fang; Qiangming Liu; Dong She; Zhiyao Dong; Zhilan Fan; Dalu Li; Hui Wang; et al. (Theoretical and Applied Genetics, 2022)
Key message SYL3-k allele increases the outcrossing rate of male sterile line and the yield of hybrid F 1 seeds via enhancement of endogenous GA 4 content in Oryza sativa L. pistils. The change in style length might be an adaptation of rice cultivation from south to north in the northern hemisphere. Abstract The style length (SYL) in rice is one of the major factors influencing the stigma exertion, which affects the outcross rate of male sterile line and the yield of hybrid F 1 seeds. However, the biological mechanisms underlying SYL elongation remain elusive. Here, we report a map-based cloning and characterisation of the allele qSYL3-k . The qSYL3-k allele encodes a MADS-box family transcription factor, and it is expressed in various rice organs. The qSYL3-k allele increases SYL via the elongation of cell length in the style, which is associated with a higher GA 4 content in the pistil. The expression level of OsGA3ox2 in pistils with qSYL3-k alleles is significantly higher than that in pistils with qSYL3-n allele on the same genome background of Nipponbare. The yield of F 1 seeds harvested from plants with 7001S SYL3−k alleles was 16% higher than that from plants with 7001S SYL3−n allele. The sequence data at the qSYL3 locus in 136 accessions showed that alleles containing the haplotypes qSYL3 AA , qSYL3 AG , and qSYL3 GA increased SYL, whereas those containing the haplotype qSYL3 GG decreased it. The frequency of the haplotype qSYL3 GG increases gradually from the south to north in the northern hemisphere. These findings will facilitate improvement in SYL and yield of F 1 seeds henceforward.

Exploratory analysis of the associations between urinary phytoestrogens and thyroid hormones among adolescents and adults in the United States: National Health and Nutrition Examination Survey 2007–2010 - Yun Fan; Hong Qian; Zhuo Wu; Zhi Li; Xiuzhu Li; Yan Zhang; Qiaoqiao Xu; Chuncheng Lu; Xinru Wang (Environmental Science and Pollution Research, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

Luteirhabdus pelagi gen. nov., sp. nov., a novel member of the family Flavobacteriaceae, isolated from the West Pacific Ocean - Wen-Ting Ren; Fan-Xu Meng; Li-Li Guo; Li Sun; Xue-Wei Xu; Peng Zhou; Yue-Hong Wu (Archives of Microbiology, 2021)
A Gram-stain-negative, aerobic, and yellow-pigmented bacterium, designated A3-108 T , was isolated from seawater of the West Pacific Ocean. Cells were non-motile and rod-shaped, with carotenoid-type pigments. Strain A3-108 T grew at pH 6.0–8.5 (optimum 6.5) and 15–40 °C (optimum 28 °C), in the presence of 0.5–10% (w/v) NaCl (optimum 1.0%). It possessed the ability to produce H 2 S. Based on the 16S rRNA gene analysis, strain A3-108 T exhibited highest similarity with Aureisphaera salina A6D-50 T (90.6%). Phylogenetic analysis shown that strain A3-108 T affiliated with members of the family Flavobacteriaceae and represented an independent lineage. The principal fatty acids were iso-C 15:0 , iso-C 17:0 3-OH, iso-C 15:1 G, and summed feature 3 (C 16:1 ω 7 c and/or C 16:1 ω 6 c ). The sole isoprenoid quinone was MK-6. The major polar lipids were phosphatidylethanolamine, one unidentified aminophospholipid, one unidentified aminolipid and one unidentified lipid. The ANIb, in silico DDH and AAI values among the genomes of strain A3-108 T and three reference strains were 67.3–71.1%, 18.7–22.1%, and 58.8–71.4%, respectively. The G + C content was 41.0%. Distinctness of the phylogenetic position as well as differentiating chemotaxonomic and other phenotypic traits revealed that strain A3-108 T represented a novel genus and species of the family Flavobacteriaceae , for which the name Luteirhabdus pelagi gen. nov., sp. nov. is proposed (type strain, A3-108 T = CGMCC 1.18821 T = KCTC 82563 T ).

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Do foreign direct investment and environmental regulation improve green technology innovation? An empirical analysis based on panel data from the Chinese manufacturing industry - Shi-Chun Xu; Yun-Fan Li; Jing-Nan Zhang; Yan Wang; Xiao-Xue Ma; Hong-Yu Liu; Hai-Ning Wang; Yuan Tao (Environmental Science and Pollution Research, 2021)

Food-grade γ-aminobutyric acid production by immobilized glutamate decarboxylase from Lactobacillus plantarum in rice vinegar and monosodium glutamate system - Li-Li Yao; Jia-Ren Cao; Chang-Jiang Lyu; Fang-Fang Fan; Hong-Peng Wang; Hong-Wei Cao; Jun Huang; Le-He Mei (Biotechnology Letters, 2021)

Enhanced β-carotene production by overexpressing the DID2 gene, a subunit of ESCRT complex, in engineered Yarrowia lipolytica - Fan Yang; Liang Liu; Shan Qiang; Ching Yuan Hu; Ying Li; Yong Hong Meng (Biotechnology Letters, 2021)

Rock physics inversion based on an optimized MCMC method - Jia-Jia Zhang; Hong-Bing Li; Guang-Zhi Zhang; Yi-Peng Gu; Zhuo-Fan Liu (Applied Geophysics, 2021)

Three new 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones and one new dimeric 2-(2-phenylethyl)chromone from agarwood of Aquilaria crassna Pierre ex Lecomte in Laos - Yang-Mei Zhao; Li Yang; Fan-Dong Kong; Wen-Hua Dong; Wei Li; Hui-Qin Chen; Hao Wang; Cai-Hong Cai; Cui-Juan Gai; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

RNA-Seq Transcriptome Analysis of the Liver and Brain of the Black Carp (Mylopharyngodon piceus) During Fasting - Ya-Fan Dai; Yu-bang Shen; Shen-Tong Wang; Jia-Hua Zhang; Yu-Hong Su; Sheng-Chen Bao; Xiao-Yan Xu; Jia-Le Li (Marine Biotechnology, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Correction to: Protein-bound calcium phosphate in uremic rat serum: a quantitative study - Hong-Xing Fan; Bao-Di Gou; Yu-Xi Gao; Gang Wu; Shu-Hu Liu; Fan Li; Tian-Lan Zhang (JBIC Journal of Biological Inorganic Chemistry, 2020)

Protein-bound calcium phosphate in uremic rat serum: a quantitative study - Hong-Xing Fan; Bao-Di Gou; Yu-Xi Gao; Gang Wu; Shu-Hu Liu; Fan Li; Tian-Lan Zhang (JBIC Journal of Biological Inorganic Chemistry, 2020)

Geographical origin differentiation of Chinese Angelica by specific metal element fingerprinting and risk assessment - Lei Sun; Xiao Ma; Hong-Yu Jin; Chang-jun Fan; Xiao-dong Li; Tian-Tian Zuo; Shuang-Cheng Ma; Sicen Wang (Environmental Science and Pollution Research, 2020)

Voxel-based morphometry results in first-episode schizophrenia: a comparison of publicly available software packages - Chen Li; Wenming Liu; Fan Guo; Xingrui Wang; Xiaowei Kang; Yongqiang Xu; Yibin Xi; Huaning Wang; Yuanqiang Zhu; Hong Yin (Brain Imaging and Behavior, 2020)

Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

NMR-based metabolomics characterizes metabolic changes in different brain regions of streptozotocin-induced diabetic mice with cognitive decline - Tingting Zhang; Hong Zheng; Kai Fan; Nengzhi Xia; Jiance Li; Changwei Yang; Hongchang Gao; Yunjun Yang (Metabolic Brain Disease, 2020)

Microencapsulation of immunoglobulin Y: optimization with response surface morphology and controlled release during simulated gastrointestinal digestion - Jin Zhang; Huan-huan Li; Yi-fan Chen; Li-hong Chen; Hong-gang Tang; Fan-bin Kong; Yun-xin Yao; Xu-ming Liu; Qian Lan; Xiao-fan Yu (Journal of Zhejiang University-SCIENCE B, 2020)

Assessing drug cue-induced brain response in heroin dependents treated by methadone maintenance and protracted abstinence measures - Xuan Wei; Wei Li; Jiajie Chen; Yongbin Li; Jia Zhu; Hong Shi; Jierong Liu; Jiuhua Xue; Wei Liu; Fan Wang; Yan Liu; Shan Dang; et al. (Brain Imaging and Behavior, 2020)

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Uptake, depuration, bioaccumulation, and selective enrichment of dechlorane plus in common carp (Cyprinus carpio) - Dapeng Wang; Hongliang Jia; Wen-Jun Hong; Xiaohong Xue; Yeqing Sun; Yi-Fan Li; Weijun Guo (Environmental Science and Pollution Research, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Expressional and Functional Verification of the Involvement of CmEXPA4 in Chrysanthemum Root Development - Hong Ren; Li-zhu Wen; Yun-hui Guo; Yuan-yuan Yu; Cui-hui Sun; Hong-mei Fan; Fang-fang Ma; Cheng-shu Zheng (Journal of Plant Growth Regulation, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Ablation of serum response factor in hepatic stellate cells attenuates liver fibrosis - Ming Kong; Wenxuan Hong; Yang Shao; Fangqiao Lv; Zhiwen Fan; Ping Li; Yong Xu; Junli Guo (Journal of Molecular Medicine, 2019)

Harnessing the Lipogenic Potential of Δ6-Desaturase for Simultaneous Hyperaccumulation of Lipids and Polyunsaturated Fatty Acids in Nannochloropsis oceanica - Fan Yang; Wasiqi Yuan; Yuhan Ma; Srinivasan Balamurugan; Hong-Ye Li; Songling Fu; Lifang Wu (Frontiers in Marine Science, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

Extraction of electron density profiles with geostationary satellite-based GPS side lobe occultation signals - Wenwen Li; Min Li; Qile Zhao; Chuang Shi; Meng Wang; Min Fan; Hong Wang; Kecai Jiang (GPS Solutions, 2019)

An emergy ternary diagram approach to evaluate circular economy implementation of eco-industrial parks - Yu Zhao; Miao Yu; Fan-wen Kong; Li-hong Li (Clean Technologies and Environmental Policy, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Effects of frequency and confining pressure on consolidation drainage behavior of soft marine clays - Yong-Hong Miao; Fan-Bo Zhou; Jie Yin; Yan-Chang Sun; Rui-Bing Li; Jian-Fei Lu (Marine Georesources & Geotechnology, 2019)

CO2 capture by ionic liquid membrane absorption for reduction of emissions of greenhouse gas - Jian-Gang Lu; Xiang Li; Yun-Xia Zhao; Hong-Lu Ma; Li-Fan Wang; Xin-Yi Wang; Yu-Fan Yu; Ting-Yu Shen; Hao Xu; Yu-Ting Zhang (Environmental Chemistry Letters, 2019)

Pharmacokinetic behaviors of ligustrazine after single- and multiple-dose intravenous Shenxiong glucose injection in rats by high-performance liquid chromatography - Qiong Wang; Huaping Sun; Li Yu; Xianpeng Ma; Baoping Jiang; Changqiong Bi; Zhihua Wang; Qinghong Fan; Yuan Yu; Yueheng Liu; Hong Nie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Inheritance patterns of anthocyanins in berry skin and flesh of the interspecific population derived from teinturier grape - Le Guan; Peige Fan; Shao-Hua Li; Zhenchang Liang; Ben-Hong Wu (Euphytica, 2019)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

Validation of reference genes for gene expression analysis of response to anthocyanin induction in cell cultures of Vitis davidii (Rom. Caill.) Foëx - Chengchun Lai; Hong Pan; Xiangui Huang; Lihua Fan; Changqing Duan; Shaozhen Li (In Vitro Cellular & Developmental Biology - Plant, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Pyrite textures and compositions from the Zhuangzi Au deposit, southeastern North China Craton: implication for ore-forming processes - Xing-Hui Li; Hong-Rui Fan; Kui-Feng Yang; Pete Hollings; Xuan Liu; Fang-Fang Hu; Ya-Chun Cai (Contributions to Mineralogy and Petrology, 2018)

Anxiolytic-like effects of paeoniflorin in an animal model of post traumatic stress disorder - Zhi-Kun Qiu; Jia-Li He; Xu Liu; Jia Zeng; Wei Xiao; Qing-Hong Fan; Xiao-Meng Chai; Wei-Hai Ye; Ji-Sheng Chen (Metabolic Brain Disease, 2018)

Exploring inhibition mechanism and nature of lipase by Ligupurpuroside A extracted from Ku-Ding tea - Yu Fan; Yang Xu; Qing-Guo Han; Liang-Liang Shen; Hong Xu; Zhi-Bing Wu; Xu Xu; Ming Ying; Zhen-Dan He; Zhang-Li Hu (Medicinal Chemistry Research, 2018)

Comparison of spatial interpolation methods for soil moisture and its application for monitoring drought - Hui Chen; Li Fan; Wei Wu; Hong-Bin Liu (Environmental Monitoring and Assessment, 2017)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

Effect of Nitrogen and Shade on Photosynthetic Gas Exchange and Productivity of Wheat Under Elevated Atmospheric CO2 Concentration - Xu-cheng Zhang; Xian-feng Yu; Hui-zhi Hou; Hong-li Wang; Yi-fan Ma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Bisphenol A Represses Dopaminergic Neuron Differentiation from Human Embryonic Stem Cells through Downregulating the Expression of Insulin-like Growth Factor 1 - Boxian Huang; Song Ning; Qinjing Zhang; Aiqin Chen; Chunyan Jiang; Yugui Cui; Jian Hu; Hong Li; Guoping Fan; Lianju Qin; Jiayin Liu (Molecular Neurobiology, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Application of high resolution SNP arrays in patients with congenital oral clefts in south China - TING-YING LEI; HONG-TAO WANG; FAN LI; YING-QIU CUI; FANG FU; RU LI; CAN LIAO (Journal of Genetics, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Identification of a divergent variant of grapevine berry inner necrosis virus in grapevines showing chlorotic mottling and ring spot symptoms - Xudong Fan; Ni Hong; Zunping Zhang; Zuokun Yang; Fang Ren; Guojun Hu; Zhengnan Li; Jun Zhou; Yafeng Dong; Guoping Wang (Archives of Virology, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

miR-105/Runx2 axis mediates FGF2-induced ADAMTS expression in osteoarthritis cartilage - Quanbo Ji; Xiaojie Xu; Yameng Xu; Zhongyi Fan; Lei Kang; Ling Li; Yingchun Liang; Jing Guo; Tian Hong; Zhongli Li; Qiang Zhang; Qinong Ye; et al. (Journal of Molecular Medicine, 2016)

Inhibition effects of high calcium concentration on anaerobic biological treatment of MSW leachate - Yi Xia; Pin-Jing He; Hong-Xia Pu; Fan Lü; Li-Ming Shao; Hua Zhang (Environmental Science and Pollution Research, 2016)

Characteristics, sources and health risk assessment of toxic heavy metals in PM2.5 at a megacity of southwest China - Youping Li; Zhisheng Zhang; Huifang Liu; Hong Zhou; Zhongyu Fan; Mang Lin; Dalei Wu; Beicheng Xia (Environmental Geochemistry and Health, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

Propofol Administration During Early Postnatal Life Suppresses Hippocampal Neurogenesis - Jing Huang; Sheng Jing; Xi Chen; Xiaohang Bao; Zhiyong Du; Hong Li; Tiande Yang; Xiaotang Fan (Molecular Neurobiology, 2016)

TNP-ATP is Beneficial for Treatment of Neonatal Hypoxia-Induced Hypomyelination and Cognitive Decline - Jie Xiao; Yilong Huang; Xia Li; Longjun Li; Ting Yang; Lixuan Huang; Ling Yang; Hong Jiang; Hongchun Li; Fan Li (Neuroscience Bulletin, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Effective conversion of maize straw wastes into bio-hydrogen by two-stage process integrating H2 fermentation and MECs - Yan-Hong Li; Yan-Xia Bai; Chun-Mei Pan; Wei-Wei Li; Hui-Qin Zheng; Jing-Nan Zhang; Yao-Ting Fan; Hong-Wei Hou (Environmental Science and Pollution Research, 2015)

Impact of diethylhexyl phthalate on gene expression and development of mammary glands of pregnant mouse - Lan Li; Jing-Cai Liu; Yong Zhao; Fang-Nong Lai; Fan Yang; Wei Ge; Cheng-Li Dou; Wei Shen; Xi-Feng Zhang; Hong Chen (Histochemistry and Cell Biology, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Saussurea medusa, source of the medicinal herb snow lotus: a review of its botany, phytochemistry, pharmacology and toxicology - Jia-Yi Fan; Hu-Biao Chen; Lin Zhu; Hong-Li Chen; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2015)

Excitotoxicity Induced by Realgar in the Rat Hippocampus: the Involvement of Learning Memory Injury, Dysfunction of Glutamate Metabolism and NMDA Receptors - Tao-guang Huo; Wei-kai Li; Ying-hua Zhang; Jie Yuan; Lan-yue Gao; Yuan Yuan; Hui-lei Yang; Hong Jiang; Gui-fan Sun (Molecular Neurobiology, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

Polycyclic aromatic hydrocarbons in Chinese surface soil: occurrence and distribution - Wan-Li Ma; Li-Yan Liu; Chong-Guo Tian; Hong Qi; Hong-Liang Jia; Wei-Wei Song; Yi-Fan Li (Environmental Science and Pollution Research, 2015)

Biodegradable composite scaffolds of bioactive glass/chitosan/carboxymethyl cellulose for hemostatic and bone regeneration - Chen Chen; Hong Li; Jianfeng Pan; Zuoqin Yan; Zhenjun Yao; Wenshuai Fan; Changan Guo (Biotechnology Letters, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Design of optimal groundwater remediation systems under flexible environmental-standard constraints - Xing Fan; Li He; Hong-Wei Lu; Jing Li (Environmental Science and Pollution Research, 2015)

Reconstruction of MODIS land-surface temperature in a flat terrain and fragmented landscape - Xiao-Mei Fan; Hong-Guang Liu; Gao-Huan Liu; Shou-Bo Li (International Journal of Remote Sensing, 2014)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Effect of temperature on development and reproduction of Proprioseiopsis asetus (Acari: Phytoseiidae) fed on asparagus thrips, Thrips tabaci - Jian Hua Huang; Shoaib Freed; Li Si Wang; Wen Jing Qin; Hong Fan Chen; Hou Guo Qin (Experimental and Applied Acarology, 2014)

Screening for Differentially Expressed Genes in Endophytic Fungus Strain 39 During Co-culture with Herbal Extract of its Host Dioscorea nipponica Makino - Chang-Hong Ding; Xiao-Wei Du; Ying Xu; Xiao-Meng Xu; Jin-Chao Mou; Dan Yu; Jun-Kai Wu; Fan-Jia Meng; Yan Liu; Wan-Li Wang; Li-Juan Wang (Current Microbiology, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

A Novel Risk Haplotype of ALOX5AP Gene is Associated with Ischemic Stroke in Chinese Han Population - Dongzhi Yang; Ying He; Manyu Li; Congcong Shi; Guoying Song; Qing Wang; Yujia Fan; Qingchuan Feng; Hong Zheng (Journal of Molecular Neuroscience, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Association between ACE I/D polymorphism and pulmonary tuberculosis in Chinese population - Yonggang Zhang; Xiaobo Li; Zhangjun Wu; Hong Fan (Molecular Biology Reports, 2014)

Analysis of the Gut Microbiota by High-Throughput Sequencing of the V5–V6 Regions of the 16S rRNA Gene in Donkey - Xinfeng Liu; Hanlu Fan; Xiangbin Ding; Zhongshan Hong; Yongwei Nei; Zhongwei Liu; Guangpeng Li; Hong Guo (Current Microbiology, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Adaptation strategies of climate variability impacts on alpine grassland ecosystems in Tibetan Plateau - Qing-zhu Gao; Yue Li; Hong-mei Xu; Yun-fan Wan; Wang-zha Jiangcun (Mitigation and Adaptation Strategies for Global Change, 2014)

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization? - Lan-Feng Xing; Yu-Li Qian; Lu-Ting Chen; Fan-Hong Zhang; Xin-Fen Xu; Fan Qu; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2014)

Potassium (K) effects and QTL mapping for K efficiency traits at seedling and adult stages in wheat - Fan-Mei Kong; Ying Guo; Xue Liang; Chun-Hong Wu; Ying-Ying Wang; Yan Zhao; Si-Shen Li (Plant and Soil, 2013)

Concentration, Sources and Human Exposure of Polybrominated Diphenyl Ethers in Indoor Dust in Heilongjiang Province, China - Ning-zheng Zhu; Hong Qi; Feng Zhang; Wan-li Ma; Li-yan Liu; Yi-fan Li (Bulletin of Environmental Contamination and Toxicology, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

Urinary Concentrations of Parabens in Chinese Young Adults: Implications for Human Exposure - Wan-Li Ma; Lei Wang; Ying Guo; Li-Yan Liu; Hong Qi; Ning-Zheng Zhu; Chong-Jing Gao; Yi-Fan Li; Kurunthachalam Kannan (Archives of Environmental Contamination and Toxicology, 2013)

TAK1 inhibitor 5Z-7-oxozeaenol sensitizes neuroblastoma to chemotherapy - Yihui Fan; Jin Cheng; Sanjeev A. Vasudevan; Roma H. Patel; Li Liang; Xin Xu; Yanling Zhao; Wei Jia; Fengmin Lu; Hong Zhang; Jed G. Nuchtern; Eugene S. Kim; et al. (Apoptosis, 2013)

Sensory–sympathetic coupling in superior cervical ganglia after myocardial ischemic injury facilitates sympathoexcitatory action via P2X7 receptor - Jun Liu; Guilin Li; Haiying Peng; Guihua Tu; Fanjun Kong; Shuangmei Liu; Yun Gao; Hong Xu; Shuyi Qiu; Bo Fan; Qicheng Zhu; Shicheng Yu; et al. (Purinergic Signalling, 2013)

The geochemical characteristics, geochronology and tectonic significance of the Carboniferous volcanic rocks of the Santanghu area in northeastern Xinjiang, China - Wei Li; YiQun Liu; YunPeng Dong; XiaoHu Zhou; XiaoMing Liu; Hong Li; TingTing Fan; DingWu Zhou; XueYi Xu; JunLu Chen (Science China Earth Sciences, 2013)

Implications for long-range atmospheric transport of polycyclic aromatic hydrocarbons in Lhasa, China - Wan-Li Ma; Hong Qi; Sonam Baidron; Li-Yan Liu; Meng Yang; Yi-Fan Li (Environmental Science and Pollution Research, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Neurotrophic Tyrosine Kinase Receptor Type 2 (NTRK2) Gene Associated with Treatment Response to Mood Stabilizers in Patients with Bipolar I Disorder - Zuowei Wang; Jinbo Fan; Keming Gao; Zezhi Li; Zhenghui Yi; Lingxiao Wang; Jia Huang; Chengmei Yuan; Wu Hong; Shunying Yu; Yiru Fang (Journal of Molecular Neuroscience, 2013)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Large-scale gold mineralization in eastern China induced by an Early Cretaceous clockwise change in Pacific plate motions - Weidong Sun; Shuang Li; Xiaoyong Yang; Mingxing Ling; Xing Ding; Liu'an Duan; Meizhen Zhan; Hong Zhang; Weiming Fan (International Geology Review, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Vulnerability window for laying male eggs and superparasitism in producing female offspring of Encarsia sophia on Bemisia tabaci B biotype - Ting-Hui Chen; Min Li; Ji-Hong Wang; Fan Zhang; Yuan-Xi Li (BioControl, 2013)

Speleothem evidence for temporal–spatial variation in the East Asian Summer Monsoon since the Medieval Warm Period - Peter C. Chu; Hong‐Chun Li; Chenwu Fan; Yong‐Heng Chen (Journal of Quaternary Science, 2012)
Published annual‐to‐decadal‐resolution stalagmite δ 18 O records since AD 900 from six caves (Dongge, Furong, Heshang, Buddha, Shihua and Wanxiang) in China were analyzed to detect temporal and spatial variability of the East Asian Summer Monsoon strength, which strongly affects wet/dry conditions in eastern China. The empirical mode decomposition method was used to obtain trends of the six cave records. After the base trend was determined, δ 18 O anomalies of each record were computed by subtracting the base trend. Mean δ 18 O anomaly values of the detrended time series for each cave record were calculated for four periods: (i) Medieval Warm Period (MWP; AD 900–1250): (ii) Little Ice Age phase 1 (LIA‐1; AD 1250–1550); (iii) Little Ice Age phase 2 (LIA‐2; AD 1550–1850); and (iv) modern period (MD; AD 1850–2000). From these anomalies, the temporal and spatial variability of wet/dry conditions has been identified. Positive values of the mean δ 18 O anomalies indicating drier conditions appeared in the lower Yangtze River Drainage Area and Southeast Coast Area during MD‐1, LIA‐1 and MWP, whereas negative values existed in north, south and Yangtze areas of eastern China during LIA‐2. The results agree with the dryness/wetness index reconstructed by Chinese historic records in general. These results illustrate that wet and dry conditions in different regions of eastern China could be opposite under monsoon influence, so that no single speleothem δ 18 O record could represent the monsoonal climate in this vast region. Climatic patterns in the monsoonal region can be either a combination of warm/wet and cold/dry or a combination of cold/wet and warm/dry on annual‐to‐centennial scales. A 128‐year periodic cycle exists in all six cave records, whereas 64‐year (possibly a harmonic of 128‐year periodicity) and 42‐year periodicities appear in Shihua, Heshang and Dongge records. These cycles may reflect the influence of solar activity on the East Asian Summer Monsoon. Copyright © 2012 John Wiley & Sons, Ltd.

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Formation of the world's largest molybdenum metallogenic belt: a plate-tectonic perspective on the Qinling molybdenum deposits - Cong-Ying Li; Fang-Yue Wang; Xi-Luo Hao; Xing Ding; Hong Zhang; Ming-Xing Ling; Ji-Bin Zhou; Yi-Liang Li; Wei-Ming Fan; Wei-Dong Sun (International Geology Review, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Important photosynthetic contribution from the non-foliar green organs in cotton at the late growth stage - Yuan-Yuan Hu; Ya-Li Zhang; Hong-Hai Luo; Wei Li; Riichi Oguchi; Da-Yong Fan; Wah Soon Chow; Wang-Feng Zhang (Planta, 2012)

The apoptosis inhibitor survivin prevents insect midgut from cell death during postembryonic development - Hong-Juan He; Li Hou; Jin-Xing Wang; Xiao-Fan Zhao (Molecular Biology Reports, 2012)

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

Overexpression of osteopontin in hepatocellular carcinoma and its relationships with metastasis, invasion of tumor cells - Fan Lin; YuYuan Li; Jie Cao; ShaoFeng Fan; JiFeng Wen; GuangHui Zhu; Hong Du; YanXiao Liang (Molecular Biology Reports, 2011)

Production and characterization of interspecific somatic hybrids between Brassica oleracea var. botrytis and B. nigra and their progenies for the selection of advanced pre-breeding materials - Gui-xiang Wang; Yu Tang; Hong Yan; Xiao-guang Sheng; Wei-wei Hao; Li Zhang; Kun Lu; Fan Liu (Plant Cell Reports, 2011)

Association of BLK (rs13277113, rs2248932) polymorphism with systemic lupus erythematosus: a meta-analysis - Ye Fan; Jin-Hui Tao; Li-Ping Zhang; Lian-Hong Li; Dong-Qing Ye (Molecular Biology Reports, 2011)

Environmental Lead Exposure Among Children in Chengdu, China, 2007–2009 - Hua Shi; Yong-mei Jiang; Jia-yuan Li; Fang Liu; Hong Wang; Fan Yu; Hui Yang (Biological Trace Element Research, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Spatial and seasonal variation of polychlorinated biphenyls in Songhua River, China - Hong You; Jing Ding; Xue-Song Zhao; Yi-Fan Li; Li-Yan Liu; Wan-Li Ma; Hong Qi; Ji-Min Shen (Environmental Geochemistry and Health, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Efficacy of Amifostine in Treating Patients with Idiopathic Thrombocytopenia Purpura - Hui Fan; Hong-Li Zhu; Su-Xia Li; Xue-Chun Lu; Bing Zhai; Bo Guo; Shan-Qian Yao; Yang Liu (Cell Biochemistry and Biophysics, 2011)

Seasonal and Spatial Variations of Air Concentrations of Polycyclic Aromatic Hydrocarbons in Northeastern Chinese Urban Region - Wan-li Ma; Hong Qi; Yi-fan Li; Li-yan Liu; De-zhi Sun; De-gao Wang; Zhi Zhang; Chong-guo Tian; Ji-min Shen (Bulletin of Environmental Contamination and Toxicology, 2011)

The −159C/T polymorphism in the CD14 gene and the risk of asthma: a meta-analysis - Yonggang Zhang; Can Tian; Jie Zhang; Xiaobo Li; Hua Wan; Chao He; Liang Guo; Quocuo Meilang; Chunhong Peng; Lina Duo; Jin Huang; Hong Fan (Immunogenetics, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Assessing the combination effects of environmental estrogens in fish - Hui Zhang; Fan-Xiang Kong; Yang Yu; Xiao-Li Shi; Min Zhang; Hong-Er Tian (Ecotoxicology, 2010)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Species and distribution of rare earth elements in the Baotou section of the Yellow River in China - Jiang He; Chang-Wei Lü; Hong-Xi Xue; Ying Liang; Saruli Bai; Ying Sun; Li-Li Shen; Na Mi; Qing-Yun Fan (Environmental Geochemistry and Health, 2010)

A Sabin 2-related poliovirus recombinant contains a homologous sequence of human enterovirus species C in the viral polymerase coding region - Yong Zhang; Fan Zhang; Shuangli Zhu; Li Chen; Dongmei Yan; Dongyan Wang; Ruiyan Tang; Hui Zhu; Xiaohui Hou; Hongqiu An; Hong Zhang; Wenbo Xu (Archives of Virology, 2010)

Type IV Pili of Acidithiobacillus ferrooxidans Are Necessary for Sliding, Twitching Motility, and Adherence - Yong-Quan Li; Dong-Shi Wan; Shuang-Sheng Huang; Fei-Fan Leng; Lei Yan; Yong-Qing Ni; Hong-Yu Li (Current Microbiology, 2010)

Anti-influenza-virus activity of total alkaloids from Commelina communis L. - Fei-Hong Bing; Jun Liu; Zhi Li; Guo-Bin Zhang; Yi-Fan Liao; Jing Li; Chang-Yuan Dong (Archives of Virology, 2009)

Polycyclic Aromatic Hydrocarbons and Polychlorinated Biphenyls in Topsoils of Harbin, China - Wan-Li Ma; Yi-Fan Li; De-Zhi Sun; Hong Qi (Archives of Environmental Contamination and Toxicology, 2009)

Effects of Nano-anatase TiO2 on Absorption, Distribution of Light, and Photoreduction Activities of Chloroplast Membrane of Spinach - Mingyu Su; Fashui Hong; Chao Liu; Xiao Wu; Xiaoqing Liu; Liang Chen; Fengqing Gao; Fan Yang; Zhongrui Li (Biological Trace Element Research, 2009)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Spatial and temporal distribution of polycyclic aromatic hydrocarbons (PAHs) in sediments of the Nansi Lake, China - Hong-Li Li; Hong Gao; Chen Zhu; Guo-Gang Li; Fan Yang; Zheng-Yu Gong; Jun Lian (Environmental Monitoring and Assessment, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Chromosomal aberrations and DNA damage in human populations exposed to the processing of electronics waste - Qiang Liu; Jia Cao; Ke Qiu Li; Xu Hong Miao; Guang Li; Fei Yue Fan; Yong Cheng Zhao (Environmental Science and Pollution Research, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Expressions of cardiac sympathetic norepinephrine transporter and β1-adrenergic receptor decreased in aged rats - He Li; Xiao-qing Ma; Fan Ye; Jing Zhang; Xin Zhou; Zhi-hong Wang; Yu-ming Li; Guo-yuan Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Polycyclic Aromatic Hydrocarbons in Urban Street Dust and Surface Soil: Comparisons of Concentration, Profile, and Source - De-Gao Wang; Meng Yang; Hong-Liang Jia; Lei Zhou; Yi-Fan Li (Archives of Environmental Contamination and Toxicology, 2009)

The effects of soy isoflavone on insulin sensitivity and adipocytokines in insulin resistant rats administered with high-fat diet - Hong-Min Zhang; Shi-Wei Chen; Li-Shi Zhang; Xiao-Fan Feng (Natural Product Research, 2008)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Characterization and selection of Lactobacillus strains for their effect on bile tolerance, taurocholate deconjugation and cholesterol removal - Min Zhang; Xiaomin Hang; Xiaobing Fan; Daotang Li; Hong Yang (World Journal of Microbiology and Biotechnology, 2008)

Production and analysis of intergeneric somatic hybrids between Brassica oleracea and Matthiola incana - Xiaoguang Sheng; Fan Liu; Yuelin Zhu; Hong Zhao; Li Zhang; Bin Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Cloning and promoter activity of rat Smad1 5′-flanking region in rat hepatic stellate cells - Yu Sun; Jianghong Fan; Hong Shen; Ping Li; Peter Cattini; Yuewen Gong (Molecular and Cellular Biochemistry, 2007)

Effects of Nano-anatase TiO2 on Absorption, Distribution of Light, and Photoreduction Activities of Chloroplast Membrane of Spinach - Su Mingyu; Hong Fashui; Liu Chao; Wu Xiao; Liu Xiaoqing; Chen Liang; Gao Fengqing; Yang Fan; Li Zhongrui (Biological Trace Element Research, 2007)

Physical mapping and identification of a candidate for the leaf rust resistance gene Lr1 of wheat - Ji-Wen Qiu; Anita Christina Schürch; Nabila Yahiaoui; Ling-Li Dong; Hua-Jie Fan; Zhong-Juan Zhang; Beat Keller; Hong-Qing Ling (Theoretical and Applied Genetics, 2007)

Cloning and characterization of a ribosomal protein L23a from Haemaphysalis qinghaiensis eggs by immuno screening of a cDNA expression library - Jinliang Gao; Jianxun Luo; Youquan Li; Ruiquan Fan; Haiping Zhao; Guiquan Guan; Junlong Liu; Bettina Wiske; Chihiro Sugimoto; Hong Yin (Experimental and Applied Acarology, 2007)

Inheritance of sugars and acids in berries of grape (Vitis vinifera L.) - Huai-Feng Liu; Ben-Hong Wu; Pei-Ge Fan; Hai-Ying Xu; Shao-Hua Li (Euphytica, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

Fog- and Rainwater Chemistry in the Tropical Seasonal Rain Forest of Xishuangbanna, Southwest China - Wen Jie Liu; Yi Ping Zhang; Hong Mei Li; Fan Rui Meng; Yu Hong Liu; Chang-Ming Wang (Water, Air, & Soil Pollution, 2005)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)